Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 130929662 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Insecta" ] } The dataset includes 130929662 records from 11898 constituent datasets: 16 records from Revision of the Australian leaf beetle genus Cheiloxena Baly, 1860 (Coleoptera: Chrysomelidae: Spilopyrinae). 2 records from A revision of the types of Heteroptera species described by Géza Horváth based on specimens from collections of Ladislav Duda and Emil Holub. 136 records from Données de la structure ACOREP provenant de la base de donnée du SINP Île-de-France CETTIA. 80 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 10 records from Waldstück Bremerhagen LK Bio Kl. 12. 117266 records from Coleção Entomológica do Museu Nacional / UFRJ. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 24 records from KUBI Paleobotany Collection. 1 records from A new species of Smicromorpha (Hymenoptera, Chalcididae) from Vietnam, with notes on the host association of the genus. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 12 records from Canadian Museum of Nature Herbarium. 409 records from A taxonomic monograph of the assassin bug genus Zelus Fabricius (Hemiptera: Reduviidae): 71 species based on 10,000 specimens. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 3 records from One new genus and species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae) from China. 3 records from A new species of Dolichopoda (Orthoptera: Rhaphidophoridae; Dolichopodainae) from Western Greece. 446 records from CNIN/Tipos Lepidoptera. 52804 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 85 records from Bannwald Burghauser Forst. 18 records from The genus Syntozyga Lower (Lepidoptera, Tortricidae) in China, with descriptions of two new species. 74 records from New species of Sericini from Sri Lanka (Coleoptera, Scarabaeidae). 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 25473 records from SEWBReC Bees, Wasps and Ants (South East Wales). 4 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 13 records from New Species and Records of Costa Rican Featherwing Beetles (Coleoptera: Ptiliidae). 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 292 records from Review of the Australian Cyllodini (Coleoptera: Nitidulidae: Nitidulinae), with descriptions of new taxa, and notes on the genus Macleayania (Nitidulini). 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 28 records from First record of the leafhopper tribe Adelungiini Baker (Hemiptera, Auchenorrhyncha, Cicadellidae: Megophthalminae) from Turkey, with notes on Achrus albicosta (Kusnezov, 1929). 199272 records from New Zealand Arthropod Collection (NZAC). 77 records from Sorensen distance for herbivores. 8947 records from Mise en place d'un suivi scientifique des odonates pour la production d’indicateurs de biodiversité. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 18 records from Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera). 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 31412 records from University of Guam Insect Collection. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 2 records from A new species of Odontothrips (Thysanoptera, Thripidae) from Fars province Iran. 32 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 12 records from Etude écologique de la Cité Scolaire Paul Valéry Paris 12ème. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 14 records from Artenvielfalt des "Grünen Klassenzimmers". 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 10 records from Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 42 records from Great British Bee Count 2015 - Stage 2 (records verified from photo). 32 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 95055 records from Sustainable Rivers Audit. 8 records from Waldsee. 2 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 8 records from Lluciapomaresius nisae, a new species of Ephippigerini (Orthoptera: Tettigoniidae: Bradyporinae) from the northeast of the Iberian Peninsula. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 9 records from Liether Park (LMS), 6c. 2971 records from ZUEC-ORT - Coleção de Orthoptera do Museu de Zoologia da UNICAMP. 2 records from Establishment of a new genus for Nudina xizangensis Fang, 2000 (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 2 records from New species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Northeastern Region of Brazil. 19 records from A revision of the genus Bryolymnia Hampson in North America with descriptions of three new species (Lepidoptera, Noctuidae, Noctuinae, Elaphriini). 1 records from Belgian IFBL Flora Checklists (1939-1971). 5 records from Additions to the leafhopper subgenus Pediopsoides (Pediopsoides) Matsumura, 1912 (Hemiptera: Cicadellidae: Macropsinae) from Southern China. 157 records from New species of gall fly (Diptera: Fergusoninidae) from Eucalyptus camaldulensis (Myrtaceae) in southern Australia and its associated parasitoids and inquilines. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 382 records from orthopteracollections-nhmj-ioj. 17 records from Notes On Claudioperla Tigrina (Klapálek) In Ecuador (Plecoptera: Gripopterygidae). 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 7 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 20 records from Collections of Bioclass, school #179, Moscow. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 718 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 4 records from A new species of Voria Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 5 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 3 records from A new species of Acrotaphus Townes (Hymenoptera: Ichneumonidae: Pimplinae) from the Brazilian Amazon, with notes on its host spider behavioral modification. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 1904 records from Escarabajos coprófagos de la cuenca alta y media del río Bita, Vichada (Colombia). 25158 records from Données multi sources collectées par Hanot Christophe, pour l'atlas des Cerambycidae de métropole (lot 2017). 4 records from NZCS Raleighvallen-Voltzberg Monitoring 1997/1998/2000/2009. 150 records from Revision of the morphology, phylogenetic relationships, behaviour and diversity of the Iberian and Italian ant-like Tachydromia Meigen, 1803 (Diptera: Hybotidae). 4 records from Dolichocaudus, a new genus in the leafhopper subfamily Evacanthinae (Hemiptera: Cicadellidae), with description of two new species. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 20 records from A new species of Lithophane Hbn. (Lepidoptera, Noctuidae, Xyleninae). 11 records from Macrobenthos Chukchi Sea, 1986. 138 records from données de la collection personnelle de CHASSAIN Jacques. 7 records from On the taxonomy and morphology of Leuthneria ruficincta (Lepidoptera: Sesiidae). 203 records from Faunistic inventory and zoogeographical analysis of the ground beetles (Coleoptera, Carabidae) of Garf Raydah Nature Reserve, Southwestern of Saudi Arabia, and description of a new species of Paussinae. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 2 records from Groehnaltica batophiloides, a new genus and species of flea-beetles (Coleoptera Chrysomelidae) from Baltic amber, described using X-ray microtomography. 90 records from St Andrews BioBlitz 2015. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 1 records from Observational database of Icelandic plants. 6 records from sarce_rockyshores. 18 records from Naturtag. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 134 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 2 records from Actualización de la Colección de Microorganismos de importancia acuática. 2 records from Morphology and molecules say: Tanytarsus latens, sp. nov. from Finland (Diptera: Chironomidae). 69097 records from ECatSym: Electronic World Catalog of Symphyta. 1 records from Atelier de malacologie continentale, 13-14 septembre (Corrèze et Dordogne). Société Limousine d’Étude des Mollusques (SLEM). 193 records from A Compendium Of Distributional Records For Oroperla Barbara Needham, 1933 (Plecoptera: Perlodidae), With Additional Documentation Of Reproductive Morphology And Biology. 265 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 123 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 72 records from The species of Symplocodes Hebard (Blattodea: Ectobiidae: Blattellinae) with description of a new species from China. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 833 records from Données de HAURAY Yann (SAPROX). 7410 records from Helgeland Museum, Lepidoptera. 203 records from Pareronia butterfly specimens at Museum Zoologi Bogor, Indonesia. 1546 records from Données d'odonates récoltées en 2013 et 2014 par le CEN Aquitaine - Suivi Temporel des Libellules (STELI) / PRAO 2013 - 2017. 1 records from -- A- - new- - species- - and- - a- - key- - to- - 10 -- species- - of- - the- - genus Lemba- - Huang, -- 1983 -- (Orthoptera Catantopidae) -- from- - China- -. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 243 records from The cicadas (Hemiptera: Cicadidae) of Peru including the description of twenty-four new species, three new synonymies, and thirty-seven new records. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1990 records from Orthoptera - SMF. 5698 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 15 records from Archilestes neblina, a new damselfly from Costa Rica, with comments on the variability of A. latialatus Donnelly (Odonata: Lestidae). 18 records from Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China. 85 records from Revision of Tynacantha Dallas with description of two new species (Hemiptera: Heteroptera: Pentatomidae: Asopinae). 1 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from University of Michigan Museum of Paleontology - Vertebrates. 2085 records from Inventaire et suivi Odonates. 958 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 11023 records from Collection Coleoptera SMF. 672 records from Colección de Entomología - Curculionidae. 841 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 71 records from Spießwoogtal / Königsbruch (Fischbach). 7 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 33 records from Description and bioecology of two new species of the genus Cryncus (Orthoptera Gryllidae, Gryllinae) from Cameroon with a key and distribution map of all African species. 1 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 12 records from List of invasive or harmful alien species in Wallis and Futuna Territory. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 47 records from Three new species and two new records of the genus Cotesia Cameron (Hymenoptera: Braconidae) from Iran. 17443 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 2 records from The beetle fauna associated with the peduncle of Sabal mexicana (Arecaceae) in southern Texas. 10 records from Revision of the " Aemilia " ambigua (Strecker) species-group (Noctuidae, Arctiinae). 1 records from Ortelsbruch - Hangmoor bei Morbach. 60 records from Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae Lamiinae) with erect setae on elytral surface. 13 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 6237 records from Plecoptera. 163 records from Données d'expertise convention GTM Bâtiment et le Service du patrimoine naturel du MNHN. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 1 records from A new species of Ferneiella from the Eocene French amber (Diptera: Scatopsidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 41 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 216 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 82 records from Taxonomic And Distributional Notes On Perlesta Teaysia, P. Golconda, And P. Shawnee (Plecoptera: Perlidae). 24 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 985 records from Bees in the UVM Zadock Thompson Zoological Collection. 5 records from NZCS Brownsberg Nature Park Monitoring. 2 records from Artenvielfalt der Nordsee - Helgoland. 1 records from ANTARCTIC PLANT DATABASE. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 2 records from Craspedorrhynchus linardii, a new species of chewing louse (Phthiraptera: Ischnocera: Philopteridae) from the Gray-headed Kite (Aves: Falconiformes: Accipitridae). 1 records from Field Museum of Natural History (Botany) Fungi Collection. 183 records from Review of the North American fauna of Drymeia Meigen (Diptera, Muscidae) and evaluation of DNA barcodes for species-level identification in the genus. 19 records from The family Bombyliidae in the Kingdom of Saudi Arabia (Diptera: Brachycera: Asiloidea). 2 records from A new species of Campylocia Needham & Murphy, 1924 (Ephemeroptera, Euthyplociidae) from Northern Brazil. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 7801 records from WildNet - Queensland Wildlife Data. 265 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 1289 records from RECORD Orthoptera Data. 15 records from New taxa of extant and fossil primitive moths in South-East Asia and their biogeographic significance (Lepidoptera, Micropterigidae, Agathiphagidae, Lophocoronidae). 1 records from National Plant Monitoring Scheme - England, Scotland, Wales. 2 records from A new fossil snipe fly with long proboscis from the Middle Jurassic of Inner Mongolia, China (Diptera: Rhagionidae). 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 7506 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 5425 records from 2020_biodiversity_information_specimen. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 149 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 1140 records from Données naturalistes de Quentin ROME. 29 records from Unraveling the white-clothed Diestostemma Amyot & Serville: a taxonomic revision of the American sharpshooters of the D. bituberculatum complex (Hemiptera: Cicadellidae). 2080 records from Données du/de la naturaliste Vindras Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 8789 records from UK Biodiversity Action Plan Invertebrate Data for Wales. 4 records from Tanycarpa broadi sp. nov., a new Neotropical species of the genus Tanycarpa Foerster, 1863 (Hymenoptera: Braconidae: Alysiinae), with a key to the New World taxa. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 206 records from Plants galls. 30 records from Artenvielfalt auf dem Schulgelände. 346 records from Neptune Deep-Sea Microfossil Occurrence Database. 2 records from The Platycerus (Coleoptera, Lucanidae) of California, with the recognition of Platycerus cribripennis Van Dyke as a valid species. 6791 records from National Museum of Natural Science. 8421 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 27 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 142 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 44088 records from Insects from light trap (1992–2009), rooftop Zoological Museum, Copenhagen. 35 records from Données de la naturaliste Laurence Beauchamp. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 13544 records from Données naturalistes de Bruno OGER. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 6 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 91 records from Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species. 1 records from Norwegian Lepidoptera working group. 2 records from A new cicada species of Psalmocharias Kirkaldy feeding on an Ephedra plant from China (Hemiptera: Cicadidae). 2 records from A new species of Plectromerus Haldeman from Central America and description of the female of Plectromerus dezayasi Nearns & Branham, 2008 (Coleoptera, Cerambycidae, Cerambycinae, Plectromerini). 318 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 4 records from Uniformus, a new genus of Dikraneurini (Hemiptera: Cicadellidae: Typhlocybinae) from China, with description of two new species. 3059 records from Calliphoridae y Mesembrinellidae (Diptera) de la Sierra Nevada de Santa Marta. 55 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 67 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 155 records from An annotated and illustrated checklist of the Indian cuckoo wasps (Hymenoptera: Chrysididae). 10 records from Taxonomic Notes On Guaranyperla (Plecoptera: Gripopterygidae). 11 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 71 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 9 records from Données naturalistes d'Olivier BARDET. 280 records from Some Museums-Meloidae-Biodiversity-Records. 11 records from Changes in the genus Beana Walker (Beaninae Zahiri & Holloway) with two new species and removing Beana nitida Tams to a new genus Beanoides (gen. nov.). 50 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 6 records from Immature stages of the genus Oxythyrea (Coleoptera: Scarabaeidae: Cetoniinae) with a key to third instar larvae, and notes on the biology of the genus. 13 records from Studies On Sweltsa Townesi And A New Species, Sweltsa Salix, From Northern California (Plecoptera: Chloroperlidae). 1330 records from Bulletin de la Société d'Histoire naturelle de Colmar. 1 records from Sächsische Schweiz (Pfaffenstein). 19 records from Naturpark Kottenforst-Ville 18.6.09. 7 records from Sertania gen. nov., a new genus of butterflies (Lepidoptera: Riodinidae) from the South American dry diagonal. 11 records from New species and records of Scaphobaeocera CSIKI from New Guinea (Coleoptera: Staphylinidae: Scaphidiinae). 3 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 3246 records from Mayfly (Ephemeroptera) records from Britain and Ireland, via iRecord. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 1 records from Die Bachspezies 2008/2009. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 22 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 81 records from Diura Washingtoniana (Hanson) Resurrected From Synonymy With D. Nanseni (Kempny) (Plecoptera: Perlodidae), Supplemented With A Description Of The Larva And Egg And Comparison To Other Congeners. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 10176 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 5 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 4 records from Données naturalistes de MICHELOT MARC. 2 records from Streuobstwiese. 33 records from Nothogreniera new genus, for two species of Australian " Paracnephia " (Diptera: Simuliidae). 6 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 93966 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 19 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 48568 records from NRW Regional Data: South East Wales Non-sensitive species. 3 records from First records of Edwardsiana sociabilis (Ossiannilsson, 1936) and Laburrus pellax (Horváth, 1903) (Hemiptera, Auchenorrhyncha: Cicadellidae) in Switzerland. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 13 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 38 records from New species and records of Paraphloeostiba Steel, 1960 from China and Laos and descriptions of four new species of related genera (Coleoptera: Staphylinidae Omaliinae: Omaliini). 59 records from Données du/de la naturaliste Wroza Stanislas provenant de la base de donnée du SINP Île-de-France CETTIA. 87 records from Larval And Egg Morphology Of Paraperla Frontalis (Banks, 1902) And P. Wilsoni Ricker, 1965 (Plecoptera: Chloroperlidae). 1 records from Hymenoptera: Eucoilinae (Cynipoidea). 2 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 1 records from A new species of the genus Sazonia O. Gorbunov & Arita, 2001 from Vietnam (Lepidoptera: Sesiidae). 4 records from Two new species of the water scavenger beetle genus Hemiosus Sharp (Coleoptera: Hydrophilidae) from Colombian Andes. 10 records from Waldstück am Schullandheim Bad Bederkesa. 120589 records from University of Hawaii Insect Museum. 3 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 168 records from Inventaire de la faune de vertébrés du Parc national du Mercantour. 10 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 36 records from Adventive Staphylinidae (Coleoptera) of the Maritime Provinces of Canada: further contributions. 12858 records from Colecção Entomológica IIA. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 2 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 3404 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 60 records from Caliroa slug sawflies of Japan (Hymenoptera, Tenthredinidae). 3 records from A New Subspecies Of Chrysolina Sanguineocincta (Crotch, 1871) From Turkey (Coleoptera: Chrysomelidae: Chrysomelinae). 1 records from Données naturalistes d'Olivier DELZONS. 53415 records from Naturalis Biodiversity Center (NL) - Diptera. 8 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 3 records from Sphaeromacrops Schillhammer new to China with description of a new species (Coleoptera, Staphylinidae). 5 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 19 records from Japanese Species of the Genus Lasconotus (Coleoptera: Zopheridae: Colydiinae), with Description of a New Species from Ishigaki-jima Island, the Ryukyu Islands. 55 records from Taxonomic revision of Guapinannus Wygodzinsky, 1951 (Hemiptera: Schizopteridae), with description of 19 new species. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 7591 records from NatureShare. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 13 records from Description of the immature and adult stages of the jujube tube spittlebug Machaerota planitiae Distant (Hemiptera: Cercopoidea: Machaerotidae) in Bangladesh. 15 records from Insect Collections of Okomu National Park- Nigeria. 237602 records from University of Minnesota Insect Collection. 29 records from A review of the stink bug genus Plautia Stål from Japan (Hemiptera, Heteroptera, Pentatomidae). 154 records from Heinersdorfer Sumpfwiese. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 1 records from Cryptotermes camelus (Isoptera: Kalotermitidae), a new drywood termite species from the Bolivian Chaco. 2 records from Asterolepis alticristata n. sp. (Antiarchi) from the Upper Devonian (Frasnian) of Nunavut, Canada, and a report on the antiarch diversity of the Fram Formation. 34 records from Bernhardsthal. 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from Naturschutzgebiet Müchelholz (Mücheln). 23 records from Wiese am Waldrand (Gurtweil). 113 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (2), 2010 - Données faune. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 2 records from Tazarcus, a new phylogenetically unplaced genus of two flightless weevils with metapleural ridge from the Eastern Arc Mountains, Tanzania (Coleoptera: Curculionidae: Molytinae). 12 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). I. Gracilipalpe, morchella and nigrum groups. 81 records from Données de la structure Communauté d’Agglomération Grand Paris Sud provenant de la base de donnée du SINP Île-de-France CETTIA. 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 2304 records from Midden-Limburg Fish Ponds Survey. 5 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 366 records from National System of Protected Areas in Poland - Animals. 9 records from Notes On Rhopalopsole Klapálek (Plecoptera: Leuctridae), With Descriptions Of Three New Species From Vietnam. 5 records from Plant specimens of Bihoro Museum. 450 records from Rhinophoridae Recording Scheme - verified via iRecord. 87 records from Redlisted beetles found in oak grove near Lake Østensjø. 895 records from Geometridae de France métropolitaine. 4 records from Description Of The Larva Of The Caucasian Species, Protonemura Bifida Martynov (Plecoptera, Nemouridae). 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 4193 records from Leicestershire and Rutland Aculeate Records. 15 records from New host and distribution records for Buprestidae (Coleoptera) from the state of Morelos, Mexico. 16618 records from Suivi Temporel des Libellules (STELI). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 14 records from The Trichoptera of Panama. XII. Contributions to the family Glossosomatidae (Insecta: Trichoptera) in Panama. 167 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 77 records from Empria and Monsoma in Japan. 11 records from Fossil Melandryidae (Coleoptera: Tenebrionoidea) from Eocene Baltic amber of the Sambian peninsula: new genus, six new species, new records and key to described taxa. 70 records from Ensemble des données Orthoptères. 5021 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas (Insectos). 3 records from Hylaperdina squamosa, a new species of Neotropical Lycoperdininae (Coleoptera, Endomychidae) from Brazil. 5 records from Pollen profile RAC20, Lake Racou, France. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 498687 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 24 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 8 records from Regenwasserabfangsbecken (Erlenbach). 77 records from SNH Invertebrate Site Condition Monitoring 2015: Perchhall Loch SSSI. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 1 records from Natura 2000 Vallée de la Seille. 10896 records from Inventario de Hymenóptera; parasítica en México. 1 records from A new species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) on fig trees in Iran. 72 records from MfN - Fossil Fish Collection. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 1 records from Morphotaxonomic revision of species-groups of Simulium (Simulium) (Diptera: Simuliidae) in the Oriental Region. 8277 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1704 records from Données naturalistes d'Anita GEORGES. 10 records from Sinopyrophorinae, a new subfamily of Elateridae (Coleoptera, Elateroidea) with the first record of a luminous click beetle in Asia and evidence for multiple origins of bioluminescence in Elateridae. 15712 records from Insect Collection of Saitama Museum of Natural History. 39 records from Synergus Hartig species group (Hymenoptera: Cynipidae: Synergini) with partially smooth mesopleurae from the New World. 308 records from Tidlig oppdagelse og varsling av fremmede arter 2020. 53 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 4 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 1 records from A new edible cricket species from Africa of the genus Scapsipedus. 6 records from Notes on the genus Perittopus Fieber, 1860 (Hemiptera: Heteroptera: Veliidae with descriptions of three new species from Indochina. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 4 records from AKG-Gelände (Bensheim). 3 records from Cyana barbora, a new species from Sichuan, southwestern China (Lepidoptera Erebidae, Arctiinae, Lithosiini). 43025 records from Cawthron Institute freshwater invertebrate data. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 2 records from Taxonomy of the Oriental leafhopper genus Parabolopona (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with a new species from China. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 43 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 1 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 39 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 33 records from The Gomphocerinae Tarbinsky, 1932 (Orthoptera: Acrididae) fauna of the Turkish Thrace. 7 records from Two new species of Quichuana Knab (Diptera: Syrphidae) from the paramo ecosystems in Colombia. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 28 records from Förderzentrum Schmölln. 1 records from Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 3 records from Allocapnia Muskogee And A. Menawa, New Species Of Snowflies (Plecoptera: Capniidae) From The Talladega National Forest Region Of Eastern Alabama, U. S. A., Plus Four New State Records. 5 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 19 records from WADFW PSAMP S1996. 43 records from Données du/de la naturaliste Jarry Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 939 records from Coléoptères Silphidés du département du Loiret. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 3 records from NZCS Sipaliwini Savanna Expeditions 1997/2014. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 8 records from Revision of the Western Palae arctic species of the genus Casinaria H (Hymenoptera, Ichneumonidae, Campopleginae). 48 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 35 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 129 records from Species of the bee genus Centris Fabricius, 1804 described by Heinrich Friese (Hymenoptera: Apidae). 222 records from Investigación Registros de Libélulas Parque Nacional Natural Tatamá 2017. 295 records from Données du/de la naturaliste Anjuerer Jack provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Two new species of Polana (Hemiptera: Cicadellidae: Iassinae: Gyponini) and redescription of Polana (Striapona) desela. 6 records from A revision of the genus Zyras (Zyras) Stephens, 1835 (Coleoptera, Staphylinidae, Aleocharinae). I. Current classification status and the redefinition of the genus. 2 records from Données espèces - Expertise IQE 35. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 2 records from Kosrae Invasive Database. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Notes on the biology and distribution of the tribe Agallissini in North America (Coleoptera: Cerambycidae: Cerambycinae). 5700 records from DDT05_2017_12_18. 13 records from Roter Berg Werdau (Leubnitz). 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 11 records from Mauernacker (Wettsaasen). 3258 records from Données naturalistes de Charlotte PICARD. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 198 records from Bruchines (Coleoptera: Chrysomelidae) associated with Senna neglecta (Vogel) H. S. Irwin and Barneby (Fabaceae: Caesalpinioideae): a new host plant for the subfamily. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 18 records from New genus to science of Meconematinae (Orthoptera: Tettigoniidae) from China with description of two new species and proposal of one new combination. 29694 records from University of California Santa Barbara Invertebrate Zoology Collection. 32 records from Wiesen in der Grünen Mitte. 47 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 6 records from Two new species and new records of the Pselaphodes - complex of genera from China (Coleoptera: Staphylinidae: Pselaphinae). 2 records from The Ceratocanthinae of Ulu Gombak: high species richness at a single site, with descriptions of three new species and an annotated checklist of the Ceratocanthinae of Western Malaysia and Singapore (Coleoptera, Scarabaeoidea, Hybosoridae). 49 records from Review of Palpostilpnus Aubert (Hymenoptera, Ichneumonidae, Phygadeuontinae), with the description of ten new species. 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 3 records from A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica. 74466 records from Entomology Collection at the Natural History Museum of Utah. 12 records from A review of the Madagascan species of the genus Cestradoretus Ohaus (Coleoptera: Scarabaeidae: Rutelinae: Adoretini). 27 records from Taxonomic notes on Sarju Ghauri, 1977 (Hemiptera: Heteroptera: Pentatomidae) with description of a new species from India. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 1 records from A new species of Cladotanytarsus (Lenziella) from Oregon supports the systematic concept of the subgenus (Diptera: Chironomidae). 142 records from Hartland Nature Club Lepidoptera Collection. 213216 records from Australian National Insect Collection. 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 27352 records from RECORD Odonata Data. 4 records from UTEP Invertebrates (Arctos). 4182 records from Diptera Collection of Museum and Institute of Zoology PAS. 125 records from SNH Invertebrate Site Condition Monitoring 2013/14: North Rothiemurchus Pinewood SSSI. 364003 records from Lithuanian Lepidoptera and Odonata. 356 records from Taxonomic revision of the species of Colletes Latreille, 1802 (Hymenoptera: Colletidae: Colletinae) found in Chile. 3 records from A new species of Polynoncus Burmeister (Coleoptera: Trogidae) from Argentina. 15 records from Schulteich Freie Waldorfschule Darmstadt. 23 records from Ostfriesland. 177 records from Données de GOUDIABY Akaren (SAPROX). 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 4 records from The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula. 1 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 23643 records from CNIN/Abejas de México/Apoidea. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 876 records from Ensemble des données Odonates. 10 records from Review of the New World genus Nanium Townes, 1967 (Hymenoptera: Ichneumonidae: Ctenopelmatinae), with two new species from the Neotropical region. 215 records from The Diptera Site. 12 records from Endogean and cavernicolous Coleoptera of the Balkans. XVII. A new species of the genus Speluncarius Reitter, 1886 (Coleoptera, Carabidae, Harpalinae, Pterostichini) from Croatia. 88 records from Identity of parasitoid wasps (Hymenoptera, Braconidae and Eulophidae) reared from aquatic leaf-mining flies (Diptera, Ephydridae) on invasive Brazilian waterweed Egeria densa in South Africa. 4 records from A new genus of Silvaninae (Coleoptera: Silvanidae) with two new species from the Malay Peninsula. 74 records from Review of the horse flies of the genus Atylotus Osten Sacken, 1876 (Diptera: Tabanidae) from Egypt, with description of a new species. 27 records from Données naturalistes de TEISSEDRE BERTRAND. 2 records from Oxybelus lusitanicus spec. nov., a new Crabronid wasp species from Portugal. 47 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 64 records from Temporal evolution of zooplankton by WP2 net in the Northwestern Mediterranean Sea, Villefranche-sur-mer 2004-2010.. 4 records from Art´n Vielfalt im Kinderwald. 294 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 80 records from Contribution to the knowledge of the dentipes group of the genus Brachiacantha (Coleoptera: Coccinellidae). 276477 records from hymenoptera. 65 records from Naturalis Biodiversity Center (NL) - Crustacea. 50 records from The West Palaearctic Dineura species, focussing on Sweden (Hymenoptera, Tenthredinidae). 12147 records from Danish Ants (Formicidae). 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 5 records from A new species of Protonemura Kempny, 1898 (Plecoptera: Nemouridae) from the Ishizuchi range, Shikoku, Japan. 24 records from Contribution to the genus Anomala Samouelle, 1819 (Coleoptera: Scarabaeidae Rutelinae) of China and adjacent regions. Part I: descriptions of two new species and remarks on four species. 70 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 216182 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 18465 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 2 records from Remarkable new fossil species of Schistostoma Becker (Diptera: Dolichopodidae Microphorinae) from mid-Cretaceous Burmese amber. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 3 records from Données malacologiques des membres du Collectif GERMAIN. 75 records from Sciences participatives sur les espèces animales introduites (EEE-FIF). 3933 records from The Broward College Insect Collection. 3896 records from Colecção Entomológica do Departamento de Sanidade Vegetal - Ministério da Agricultura e Segurança Alimentar. 125 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 11 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 8 records from Schulgarten mit Klasse 8a (Essen). 19 records from Pterophoridae (Lepidoptera) fauna of the Republic of Tuva. 58 records from Cephalomalthinus simplicicornis (Wittmer, 1993) rev. stat. et comb. n.: a resurrected soldier beetle (Coleoptera, Cantharidae) from Taiwan based on morphological and molecular data. 54 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 2926 records from Ecosphère_2017_12_18. 1 records from Description of a new species of Hyalinocerus (Hemiptera: Cicadellidae) from southwestern China, with an update on the generic diagnosis. 473 records from Données du/de la naturaliste Tellez David provenant de la base de donnée du SINP Île-de-France CETTIA. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 2 records from The second species of Phanoperla (Plecoptera: Perlidae) from China, P. hainana sp. nov., from Hainan Island. 114 records from Fermanagh Flora. 9 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 1 records from Description of the adult and larva of Clunio balticus Heimbach, 1978 (Diptera Chironomidae) from the seashore of Bergen (Norway). 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 5 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 18 records from An annotated checklist of the Iranian Brentidae (Coleoptera: Curculionoidea). 6 records from Historic Lady Beetle Records (Coccinellidae) from Mt. Mansfield, Vermont , USA: 1991-1994. 2 records from New record of the steppe longhorn beetle species Phytoecia (Musaria) argus (G. F. Frölich, 1793) (Cerambycidae: Lamiinae) in Bulgaria. 2 records from An interesting new species of Kamimuria (Plecoptera: Perlidae) from China, with notes on K. grandispinata Du & Sun. 1037 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 723 records from Lothian Wildlife Information Centre Secret Garden Survey. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 47 records from Narrow-winged pyralids (Lepidoptera, Pyraloidea, Pyralidae, Phycitinae) of Leningrad Province and the city of St. Petersburg, Russia. 2 records from Marthamea bayae, a new species of stonefly from Algeria (Plecoptera: Perlidae). 2 records from Schizopyga alinae, a genus of pimpline parasitoid wasps (Hymenoptera: Ichneumonidae: Pimplinae) new to the Afrotropical region. 4 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 2 records from A new record of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from Northern Vietnam with description of two new species. 49 records from Calvariopsis gen. nov., a new genus of Neotropical Scirtidae (Coleoptera: Scirtoidea). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 52608 records from Insects, Outer Hebrides. 64 records from Review of the genera Pristocera Klug and Pristepyris Kieffer (Hymenoptera Bethylidae, Pristocerinae) of Russia and adjacent territories. 1 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 2 records from A New Genus And Species Of Panaphantina (Coleoptera: Staphylinidae: Pselaphinae: Euplectitae: Trichonychini) From Australia. 47 records from A study on the genus Stenus Latreille from Zhuji City of Zhejiang, East China (Coleoptera, Staphylinidae). 43 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 16 records from An der Ohm, (Wettsaasen). 4 records from Anisops sardeus Herrich-Schaeffer, 1849: first records from Hungary (Heteroptera: Notonectidae). 185 records from Inventaire des odonates d'intérêt communautaire. 506 records from Hexapoda MZS. 2112 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 3 records from New species of Lonchaeidae (Diptera) from Switzerland and Serbia with arevised checklist of the Swiss fauna. 1 records from A new species of Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae; Conocephalinae; Copiphorini) from India. 6 records from Nova espécie de Euschistus (Mitripus) da Argentina e sul do Brasil (Hemiptera, Pentatomidae, Pentatominae). 414 records from Gurgltal (Tarrenz). 12 records from Contributions to the knowledge of the Aleocharinae (Coleoptera, Staphylinidae) in the Maritime Provinces of Canada. 25 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 133 records from Données du/de la naturaliste Duret Bertrand provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Papilio Sticheli nov. spec. aut subsp.. 306 records from Revision of the genus Platyscelis Latreille, 1818 from China (Coleoptera: Tenebrionidae: Platyscelidini). 32 records from Australian Marsh Beetles (Coleoptera: Scirtidae). 9. The relations of Australasian Ypsiloncyphon species to their Asian congeners, additions, mainly to Petrocyphon and Prionocyphon, and a key to Australian genera of Scirtinae. 3253 records from Hemiptera: Auchenorrhyncha: Records for Kent. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 8177 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 10 records from Meadow katydids (Orthoptera: Tettigoniidae: Conocephalini) from the Central-West Region of Brazil: Morphological, bioacoustic and cytogenetic study. 1 records from Additions to the taxonomy of the Afrotropical Tetramorium weitzeckeri species complex (Hymenoptera, Formicidae, Myrmicinae), with the description of a new species from Kenya. 34 records from ZUEC-EPH - Coleção de Ephemeroptera do Museu de Zoologia da UNICAMP. 85 records from A review of Spathipheromyia (Diptera: Muscidae) from Argentina with the description of an extra-large new species. 1257 records from Bumble bees collected in a large-scale field experiment in power line clearings, southeast Norway. 436 records from Données du naturaliste Danten Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species of the genus Mawenzhena Alexis & Delpont (Coleoptera Scarabaeidae: Cetoniinae: Goliathini) from South Korea. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5817 records from New Mexico Museum of Natural History and Science (NMMNHS) Insect specimens (Arctos). 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 6010 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 42 records from The apterous endemic genus Omphra Dejean (Coleoptera: Carabidae: Helluonini) of the Indian subcontinent: taxonomy with notes on habits and distributional patterns. 1 records from Erpetogomphus oxybelis sp. nov. from Veracruz, Mexico (Odonata: Gomphidae). 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 14 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 451 records from Données rhopalocères. 38 records from First study of fungus gnats (Insecta: Diptera: Sciaroidea) in Tisata Reserve (SW Bulgaria). 607 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 9 records from Discovery of the genus Pseudepione Inoue, 1943 in Taiwan, with description of a new species (Lepidoptera: Geometridae: Ennominae). 138 records from Thibaut_LACOMBE_2017_12_18. 1 records from Colección de Bacterias del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 2293 records from Données faune ZNIEFF de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 1 records from New Afrotropical species of the genus Coridiellus J. A. Lis, 1990 with a key to its species (Hemiptera: Heteroptera: Dinidoridae). 6566 records from CABI Lepidoptera Collection. 2 records from A new species of Bruchomyiinae (Diptera: Psychodidae) from Baltic amber. 4 records from Two remakable new species of Notocera Amyot and Serville, 1843 (Hemiptera, Membracidae, Hypsoprorini) from the Brazilian Caatinga. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 103979 records from University of Guelph Insect Collection (DEBU). 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 88 records from California Soliperla Ricker, 1952 (Plecoptera: Peltoperlidae), Distribution And Taxonomic Characters. 137 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 13 records from Junge Heide, Radebeul/Dresden. 1 records from Revision and redefinition of the crematogastrine ant genus Tetheamyrma BOLTON, 1991, with the description of a new species and the first description of the dealate queen (Hymenoptera: Formicidae). 3131 records from Solitary bees collected in a large-scale field experiment in power line clearings, southeast Norway. 8 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 18 records from Naturgrundstück (Eutin). 809 records from ant-plant_symbioses. 1 records from Epimecia tekes, a new species from south-eastern Kazakhstan (Lepidoptera Noctuidae, Oncocnemidinae). 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 1 records from Red Sea microbial plankton Raw sequence reads. 30 records from New species of Hercostomus Loew, 1857 (Dolichopodidae, Diptera) from Japan. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 1785 records from Transferts SI Faune - Données naturalistes opportunistes de Sylvain BONIFAIT. 2 records from A new genus, Perplexacara, and new generic placements of species of Australian marsh beetles (Coleoptera: Scirtidae) based on morphology and molecular genetic data. 48 records from Parc_Naturel_Régional_des_Préalpes_d'Azur_2017_12_18. 68531 records from MDFRC macroinvertebrate survey. 15 records from Amtsrain Apolda-Zottelstedt. 2 records from Ukamenia Oku, 1981 (Lepidoptera: Tortricidae: Olethreutinae), new record for Thailand with descriptions of a new species. 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 228 records from MoJ BioBlitz August 2018. 46 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 1 records from GEO-Hauptveranstaltung Bodden (Vilm). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 5 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 6 records from Review of Holophris Mocsáry (Hymenoptera: Chrysididae) from Vietnam, with description of a new species. 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 2 records from Descripción de una nueva especie del grupo Drosophila tripunctata (Diptera: Drosophilidae) en Cruz Loma, Pichincha, Ecuador. 1 records from New record of the genus Bambusiphaga (Hemiptera: Delphacidae: Tropidocephalini) from India with description of a new species. 2 records from RECORD Vascular Plant Data. 127 records from Family groups of Diopsoidea and Nerioidea (Diptera: Schizophora) - Definition, history and relationships. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 10 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 17322 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 172 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 4 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 191 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 942 records from New data on the dragonfly fauna of the Moulouya River Basin and the Oriental Region, Morocco (Odonata). 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 48 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5 records from A new genus and two new species of arctiine tiger moth (Noctuidae, Arctiinae, Arctiini) from Costa Rica. 1352 records from Studies on the Australian Muscidae (Diptera). VIII. The genus Lispe Latreille, 1797. 2 records from Youngest representative of the extinct genus Microphorites in the Eocene amber of France (Diptera: Dolichopodidae: Microphorinae). 29876 records from European Moth Nights. 50 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 1419 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 1 records from First record of the genus Genaemirum (Hymenoptera, Ichneumonidae, Ichneumoninae) from West Africa, with the description of a new species from Guinea. 5886 records from Solitary Bees and Bumblebees in a Danish Agricultural Landscape - data from PhD-study. 33177 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 3 records from Données naturalistes de THÉVENOT Jessica. 100 records from Re-classification of Lycoriella Frey sensu lato (Diptera, Sciaridae), with description of Trichocoelina gen. n. and twenty new species. 57 records from A revision of the genus Hypotrix Guenee in North America with descriptions of four new species and a new genus (Lepidoptera, Noctuidae, Noctuinae, Eriopygini). 127 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 963 records from University of Western Ontario Collection. 8 records from Sandsitermes gen. nov., a new nasute termite genus from South America (Isoptera, Termitidae, Nasutitermitinae). 20 records from Wiese und Weide am Waldrand von Gusterath. 817 records from Lucanidae. 10 records from SyNoeca ilheeNsis sp. nov., a new social wasp (Hymenoptera, Vespidae, Polistinae) from Brazilian lowland Atlantic Forest. 81 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 54 records from Unna-Mühlhausen, Wiesen. 264 records from IBF Monitoring of Plant Galls. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 2 records from Designation Of A Replacement Name For Capnioneura Veronicae Nomen Nudum (Capniidae Plecoptera). 265955 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Discovery of two new Andean species of Scolomus (Townes & Townes), with a key to all known species (Hymenoptera: Ichneumonidae: Metopiinae). 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 1 records from W herbarium - Naturhistorisches Museum Wien - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 101 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 1 records from Genebank, National Institute of Agrobiological Sciences. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 4 records from Two new species of Psephenops Grouvelle (Coleoptera: Byrrhoidea: Psephenidae) from Panama. 10087 records from River Biologists' Database (EPA). 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 1 records from Great Eastern Ranges - Slopes to Summit. 97825 records from Tiroler Landesmuseum Ferdinandeum. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 10 records from Tongrube bei Hettstedt. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 5583 records from Données faune Nature 18 - 2017. 8851 records from Odonata records from RSPB Reserves 1970-2009. 102 records from Twenty new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental Region. 2 records from Description of the female and egg of Phantasca phantasma (Westwood, 1859) (Phasmatodea: Diapheromeridae: Diapheromerinae). 29 records from Incriminacion De Vectores De Leishmaniasis En La Costa Caribe. 18 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 158 records from The genus Anisoscelis Latreille (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini): new species, taxonomical arrangements, distributional records and key. 3 records from Notes on west Palaearctic species of the genus Trigonurus Mulsant, 1847 (Coleoptera: Staphylinidae: Trigonurinae). 2 records from The first Cacomorphocerus species (Coleoptera, Cantharidae) from Rovno amber a second species of the genus with 11 - segmented antennae. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 3 records from Protist Diversity in the East China Sea. 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 8 records from Données espèces - Expertise IPE 79. 11 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 1010351 records from NBIS Records to December 2016. 2 records from A new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from Morocco. 39 records from The genera and species of the Brueelia - complex (Phthiraptera: Philopteridae) described by Mey (2017). 48 records from A new species of Metrobates Uhler, 1871 (Hemiptera: Heteroptera: Gerridae) from Colombia. 89 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 1678 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 4 records from Redescription of three species of Apobaetis Day, 1955 (Ephemeroptera: Baetidae). 1 records from South American Antarctic Marine Biodiversity Literature. 47 records from A catalog of Acroceridae (Diptera) from Chile. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 32 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 4 records from Cylindera (Conidera) mindoroana sp. n. (Coleoptera: Cicindelidae), a new tiger beetle species from the Philippines. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 7157 records from Données naturalistes de MOREAU Patrice. 31 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 8 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 8 records from A revision of African Psammoecus (Coleoptera, Silvanidae) and descriptions of two new species from the collection of the Musée royal de l’Afrique centrale. 237 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from A New Record From The Genus Callicera Panzer, 1809 (Insecta: Diptera: Syrphidae) From India. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 641 records from Observations naturalistes des Amis de BioObs.. 3 records from Description of a new species of the genus Maua Distant (Hemiptera, Cicadidae) from China. 13 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 17520 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 472 records from Données naturalistes d'Aurélie CHEVILLON. 8170 records from NE Scotland other invertebrate records 1800-2010. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 113 records from Registro de una poblacion de Abejorros en los departamentos de Boyacá y Cundinamarca. 13 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 12 records from Dimitri Multeau Loir-et-Cher Nature. 98 records from Données opportunistes sur les odonates. 28 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from A new species of the genus Nenasa (Hemiptera: Fulgoroidea: Caliscelidae) from mainland China. 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 16742 records from Données Entomologiques A. HORELLOU 1988-2018. 163 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 26 records from A new species of Tricorythodes Ulmer (Ephemeroptera: Leptohyphidae) from Uruguay. 12 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 1370 records from EXPLOR'NATURE 2018, inventaire biologique de la commune de Sospel. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 2 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 31 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 256 records from EDIT - ATBI in Gemer area (Slovakia). 22137 records from Global compendium of Aedes albopictus occurrence. 1 records from Inventaire malacologique de la RNR des Marais de Stors. 112 records from A revisional study of the Chinese species of Amphiops Erichson (Coleoptera, Hydrophilidae, Chaetarthriini). 1 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 28 records from Teich Berlin Wuhlheide. 1676590 records from Natural History Museum (London) Collection Specimens. 56 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 20 records from Ried und Sand - Artenvielfalt durch Beweidung. 1 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Taiwan, with keys to all 13 species of the Simulium varicorne species-group. 104 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 18 records from RSCROP: Desert Locust Monitoring, Forecasting and Assessment in Africa and Asia Archive from 2018-01-01 (Ongoing). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 34 records from Taxonomic review of Athliini (Coleoptera: Scarabaeidae: Melolonthinae), a new tribe of scarab beetles endemic to South America. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 31 records from The genus Stactobiella Martynov (Trichoptera, Hydroptilidae) in Japan. 30 records from Two New Species Of Stoneflies In The Leuctra Ferruginea Group (Plecoptera: Leuctridae), With Notes On The Leuctra Species Known For Mississippi And Alabama, U. S. A.. 75 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 324 records from BUND - Dassower See (Lübeck/Dassow). 58755 records from Données naturalistes de Monsieur François FOURNIER. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 6 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 142 records from Three new species, Elathous zagrosensis sp. n., Zorochros dilatatus sp. n., and Dicronychus iranicus sp. n., and noteworthy records of click beetles from western Iran (Coleoptera: Elateridae). 5 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 2 records from Two new species of the Rhyacophila nigrocephala species group from China (Insecta, Trichoptera, Rhyacophilidae). 3 records from An annotated checklist of the psyllids of New Zealand (Hemiptera: Psylloidea). 2 records from A new species of Leptomenes Giordani Soika from Uganda (Hymenoptera Vespidae: Eumeninae). 8 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 210 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 87 records from Barsura Volynkin, Dubatolov & Kishida, gen. nov., with descriptions of three new species (Lepidoptera, Erebidae, Arctiinae). 35 records from A review of the genus Trachystolodes Breuning, 1943 (Coleoptera: Cerambycidae Lamiinae: Lamiini). 132984 records from Hatikka Observation Database. 266 records from Données naturalistes de Monsieur JOURDE Rémi. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 2088 records from OSAC North American Cossoidea -beta version. 115425 records from inatura - Erlebnis Naturschau Dornbirn. 7 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 92 records from DNA Barcoding and Integrative Taxonomy of the Heterolepisma sclerophylla species complex (Zygentoma: Lepismatidae: Heterolepismatinae) and the Description of Two New Species. 17 records from New species of Euphorinae parasitoids of the family Braconidae (Hymenoptera) from South Korea. 207 records from Images and observations of mostly edible plants in Stephen Barstow’s Edible Garden in Norway, taken between 2005 and 2014. 2 records from LSUMZ Mammal Tissues. 6 records from A new species in the Trachusa ovata species group (Hymenoptera: Apoidea) from Peninsular Malaysia with an overview of the old-world species within the genus Trachusa. 2 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 12 records from Description of three new species of biting midge of the genus Atrichopogon Kieffer (Diptera: Ceratopogonidae) from Brazilian Amazon. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 1 records from Megacraniinae-The Palm Stick Insects: A new subfamily of Old World Phasmatodea and a redefinition of Platycraninae Brunner v. Wattenwyl, 1893 (Phasmatodea: “ Anareolatae ”). 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 9 records from New species and stages description of Traverella Edmunds, 1948 (Ephemeroptera Leptophlebiidae) from Northeast Brazil. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from NSW AVH data. 5 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 106597 records from Database of invertebrates collected in Mongolia. 32853 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 1 records from DNA barcodes and morphology confirm a new species of Rheocricotopus (Psilocricotopus) orientalis group (Diptera: Chironomidae). 157 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 2970 records from WTSWW Data: All Taxa (West Wales). 432 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 14 records from "Ahrschleife bei Altenahr". 99687 records from South Australian Museum Australia provider for OZCAM. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 6 records from New anaxyelids (Hymenoptera: Anaxyelidae) from the Cretaceous of Asia. 1 records from A new species of Tapiena (Orthoptera: Tettigonioidea: Phaneropterinae) from Brunei Darussalam (Borneo, Southeast Asia). 67 records from Three new ghost moths of the genus Oxycanus Walker, 1856 from Australia (Lepidoptera: Hepialidae). 6066 records from Communities of ground beetles (Carabidae, Coleoptera) in broad-leaved forests of protected and urban areas of the Kaluga Oblast (European Russia). 20 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 22 records from Descriptions of eight new species of the genus Parancistrocerus Bequaert (Hymenoptera: Vespidae: Eumeninae), with a key to the Oriental species. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 26 records from Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China. 30 records from Unter hellen Zinnen und finsteren Grotten. 598 records from BCE butterfly data in and around Nothern Italy. 1 records from Diverse mechanisms of feeding and movement in Cyclorrhaphan larvae (Diptera). 4 records from Haruchlora maesi, a new emerald moth genus and species from Mesoamerica (Lepidoptera, Geometridae, Geometrinae). 18 records from Colaphellus palaestinus Achard, a new leaf-beetle for Europe (Coleoptera, Chrysomelidae, Chrysomelinae). 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 256 records from Reevaluation of species richness in Winnertzia (Diptera, Cecidomyiidae, Winnertziinae), with descriptions of 37 new species from Sweden, Peru and Australia. 56 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 10 records from Taxonomic revision of the microleafhopper subgenus Alnetoidia Dlabola from Korea (Homoptera: Cicadellidae: Typhlocybinae). 2 records from The genus Eodendrus Belokobylskij (Hymenoptera, Braconidae, Doryctinae) from China, with description of a new species. 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 1924 records from Modernisation des ZNIEFF du PnrL. 22 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 46 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 179 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 3 records from A new species of the genus Colilodion Besuchet, 1991 (Coleoptera: Staphylinidae: Pselaphinae) from Mindanao, the Philippines. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3 records from Description of the mature larva of Austrolimnius nyctelioides (Germain, 1892) and A. elatus Hinton, 1941 (Coleoptera: Elmidae). 7 records from Museu Paraense Emílio Goeldi - Paleoinvertebrate Collection. 93 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 9 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 2318 records from Données naturalistes de Bernard Lalanne-Cassou. 228 records from Bird Collection of Museum and Institute of Zoology PAS. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 9 records from Morphological description and DNA barcoding of Hydrobaenus laticaudus Saether 1976 (Diptera: Chironomidae: Orthocladiinae) from Amur River basin (Russian Far East). 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 382 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1642 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 7 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 1 records from Adamastoraltica humicola, new genus and new species: the first example of possible moss-inhabiting flea beetle genus from sub-Saharan Africa (Coleoptera Chrysomelidae, Galerucinae). 1 records from Lissotes working-group. 94 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 41 records from Die Teiche im Britzer Garten. 7606 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from Description of a new species resembling Paratrichius circularis Ma, 1990 (Coleoptera: Scarabaeidae: Cetoniinae) from China. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 6 records from Two new species of the genus Gibbotettix Zheng, 1992 (Orthoptera: Tetrigidae, Cladonotinae) from China. 12 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 4612 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 13 records from MfN - Fossil vertebrates IV. 72 records from Swedish Malaise Trap Project (SMTP) - Xoridinae. 37 records from Cladistics and revision of Alitocoris with considerations on the phylogeny of the Herrichella clade (Hemiptera, Pentatomidae, Discocephalinae, Ochlerini). 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 69 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 10 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 11 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 7 records from Description of New Miridae and Tingidae Species (Hemiptera: Heteroptera) and New Records from Southern Turkey. 240 records from Taxonomy and natural history of the myrmecophilous genus Clinterocera Motschulsky, 1858 (Coleoptera: Scarabaeidae: Cetoniinae) from China and adjacent regions: revision of the C. jucunda species group. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 1 records from New species and new record of Thraulodes Ulmer, 1920 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) from Brazil. 9 records from First record and new species of the Oriental leafhopper genus Trifida Thapa & Sohi (Hemiptera: Cicadellidae: Typhlocybinae) from China. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 24 records from Vermont Oil Beetle Records from Pinto and Selander 1970. 1 records from Developmental Biology among Corbiculate Bees: Bombus impatiens, Including Observations on Its Egg Eclosion. 12 records from Towards the taxonomy of Corynoneura Winnertz (Diptera: Chironomidae: Orthocladiinae) from the Russian Far East and Eastern Siberia. 21 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 19 records from A new species of Oryttus Spinola, 1836 from the United Arab Emirates and Tunisia with identification key to Palaearctic species (Hymenoptera, Crabronidae). 1 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 316 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 3 records from Miltochrista wangmini, a new species from China (Lepidoptera, Erebidae, Arctiinae). 3 records from Données opportunistes collectées par les agents du Département des Landes. 1480 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 62 records from Nomenclatural changes in American Apomecynini including description of new genera and species (Coleoptera: Cerambycidae). 7 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 94 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 13 records from A new stiletto fly genus from South America (Diptera: Therevidae: Agapophytinae). 2 records from A new species of Aegidium Arrow (Coleoptera: Scarabaeidae: Orphninae) from Colombia. 7 records from Records And Descriptions Of Some Nemouride Species (Order: Plecoptera) From Leigong Mountain, Guizhou Province, China. 7 records from New Species Of Tyloperla (Plecoptera: Perlidae) From Vietnam And Thailand. 1036 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 95 records from Vorderer Tiergarten (Dessau). 238 records from Données naturalistes d'Olivier LAURENT. 3 records from Kindergarten. 13 records from Coleção de Coleoptera da Universidade de Brasília. 590 records from New synonyms, combinations and status in the Chinese species of the family Meloidae Gyllenhal, 1810 (Coleoptera: Tenebrionoidea) with additional faunistic records. 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 3 records from Wuhle - Brücke / B1. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 48 records from SNH Invertebrate Site Condition Monitoring 2015: Tweedwood - Gateheugh SSSI. 1641 records from 2019_biodiversity_cooperation_investigation. 54 records from Jeff Ogden Collection. 1 records from Eminepygia myanmarensis sp. nov., a new Earwig (Dermaptera) Nymph in Burmese Amber. 1159 records from National Benthic Inventory. 70 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 1 records from First record of the cicadas genus Orientopsaltria Kato, 1944 (Hemiptera: Cicadidae) from Vietnam, with description of one new species. 98 records from Données de la naturaliste Clémentine Gand. 17 records from Three new species of genus Mecopoda Serville, 1831 from China (Orthoptera: Tettigoniidae: Mecopodinae). 2 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 13381 records from BCE butterfly data expert holiday data throughout Europe. 54 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 17764 records from National River Water Quality Network Database (Macro-invertebrates) 1990-2008. 18 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 2 records from A new apterous genus of Carventinae from China (Hemiptera: Heteroptera Aradidae). 91 records from Review of the species of Stenothemus from Southeast China (Coleoptera, Cantharidae). 1947 records from Arthropods from Praia da Vitória (Terceira, Azores, Portugal). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 2 records from Trachelus stipa (Hymenoptera: Cephidae), a new stem sawfly from Central Anatolia associated with feather grass (Stipa holosericea, Poaceae). 1037 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 3 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 64 records from Revision of the Barsine cardinalis - anomala ' species-complex' (Lepidoptera, Erebidae, Arctiinae). 4 records from Rearrangements in some species groups of Amblycerus Thunberg, 1815 (Coleoptera: Chrysomelidae: Bruchinae) including keys, description of a new species, new host plant and distributional records. 45 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 10 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 2737 records from Manx Biological Recording Partnership UNVERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 10 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 5 records from Escarabajos longicornios (Coleoptera: Cerambycidae y Disteniidae) del Parque Nacional Darién, Panamá. 13 records from verschiedene Kleingewässer um Oldenburg/Holstein. 21 records from DSMZ Bacteria. 253270 records from CAS Entomology (ENT). 13292 records from CNIN/Thysanoptera. 4 records from The First Record Of A Far East Stonefly (Plecoptera) From Central Asia. 68975 records from Carnet B Lorraine. 18 records from Swedish Malaise Trap Project (SMTP) - Diacritinae. 118 records from Naturalis Biodiversity Center (NL) - Pisces. 2075 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 2968 records from John Clayton's Fijian Moth Collection. 87 records from The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species. 25 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 12342 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Seasearch Marine Surveys in England. 26 records from Données du/de la naturaliste PRATTE Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 299 records from Insect Ichneumon fly (KIDR-IN). 47 records from A taxonomic revision of the genus Sirthenea (Hemiptera: Heteroptera: Reduviidae) of the Old World. 14 records from On the taxonomy of the genus Neadeloides Klima, 1939 (Crambidae: Pyraustinae) with description of a new species from India. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 60378 records from Insect specimens of Tochigi Prefectural Museum. 13714 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 39 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 4172 records from VIT - Lepidotheca (The Natural History Museum of Álava). 1 records from Three new species of the family Scathophagidae (Diptera) from the Palaearctic region with a redescription of the male of Amaurosoma longicorne. 3 records from A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae). 10 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 45 records from Genera and species of the Liothrips lineage (Thysanoptera, Phlaeothripinae) from Taiwan. 126 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 133767 records from Arizona State University Hasbrouck Insect Collection. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 3 records from Herbarium Amazonense. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 6 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 57 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 156 records from Chironomid remains in the sediment sequence of Site PG1212. 2 records from A remarkable new species of Phocides (Lepidoptera: Hesperiidae) from Bolivia and taxonomic considerations on Phocides charon. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 1 records from A new species and a new record of Horaeomorphus Schaufuss (Staphylinidae: Scydmaeninae: Glandulariini) from China. 78 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 17 records from Heavy minerals of sediment core PL94-64. 7 records from Pycnogaster ribesiglesiasii, a new species of Ephippigerini (Orthoptera: Tettigoniidae: Bradyporinae) from Catalonia (northeast of the Iberian Peninsula). 2100 records from Dolichopodidae of Portugal - dataset 2009-2018. 7805 records from Noctuoidea de France métropolitaine. 9 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 58 records from Données du/de la naturaliste Provost Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 59 records from Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species. 60 records from New species, a new combination, and a new country record in American Clytini (Coleoptera: Cerambycidae: Cerambycinae). 7 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 2922 records from Données naturalistes d'Alain BERLY. 39012 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 3 records from Gastrotermes spinatus gen. n. sp. n., an African soil-feeding termite described from the worker caste (Isoptera, Termitidae, Apicotermitidae). 197 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 279 records from Ville de Trois-Rivières - Bioblitz 2012. 25 records from Mantidflies (Neuroptera, Mantispidae) from Tocantins state (Brazil): distribution and identification key. 29 records from Inventaire de l'îlot du Lédénez Vraz. 530 records from Données opportunistes. 2 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 6 records from A new fossil species of Trentepohlia (Diptera, Limoniidae) from the Dominican Miocene. 54 records from Inventaire et regroupement de données Natura 2000. 16 records from The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species. 30 records from Four new species of Myrsidea (Phthiraptera: Amblycera: Menoponidae) from Chinese babblers (Passeriformes: Leiothrichidae, Paradoxornithidae, Timaliidae). 17 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 1 records from Description of a new species of the genus Mongolotettix Rehn, 1928 (Orthoptera: Acrididae) from Fujian, China. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 18 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 92 records from Colectas del género Ischnura en el marco del proyecto Divergencia genética y preferencia de apareamiento en Ischnura capreolus e Ischnura cyane en Colombia. 2 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 1702 records from DREAL Auvergne - Insectes - 2015. 83 records from Taxonomic study of the genus Hypatopa Walsingham, 1907 (Lepidoptera: Blastobasidae) in China, with descriptions of five new species. 3 records from A new species of Colacus Ohaus, 1910 (Coleoptera: Scarabaeidae: Dynastinae) from the Mata Seca biotope of Brazil, and notes on Colacus morio Ohaus, 1910. 3738 records from Données opportunistes fortuites sur les rhopalocères récoltées lors des prospections terrains. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 3 records from Contribution to the knowledge of Dialeurodes (Gigaleurodes) Quaintance & Baker (Hemiptera: Aleyrodidae), with description of a new species from China. 23 records from Taxonomic revision of Plyomydas Wilcox & Papavero, 1971 with the description of two new species and its transfer to Mydinae (Insecta: Diptera: Mydidae). 289 records from bmhs_butterfly_collection. 7 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 4 records from A new black fly species of Simulium (Simulium) (Diptera: Simuliidae) from Taiwan. 42 records from Pöhlberg bei Annaberg. 4 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 4 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1 records from SWECO. 1329 records from Données naturalistes de Loïc SALAUN. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1 records from Discovery of termitophilous tenebrionid beetles in China (Coleoptera: Tenebrionidae). 395 records from Suivi Odonates. 2321 records from Dataset of fungus gnats (Diptera,Sciaroidea) from Møre og Romsdal county in Norway. 577 records from East Ayrshire Species Database. 3 records from Systematics of Helioandesia tarregai gen. et sp. nov. (Lepidoptera: Yponomeutoidea: Heliodinidae) from the Andes of Northern Chile. 100 records from Euroants. 8006 records from Knerer collection / Gschwendtner property. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1564 records from Leif Richardson Vermont Bee Specimens. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 2 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 1 records from Description of a new neotropical species of Xiqilliba Kramer (Hemiptera: Cicadellidae: Neocoelidiinae). 7 records from Collection Crustacea - ZMB. 2 records from Ceraphron krogmanni (Hymenoptera: Ceraphronidae), a new species from Lower Saxony with unusual male genitalia. 170 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 105 records from Abundanz_Infloreszenzenschlupf_Pflanzenebene_2008. 62 records from Suivi des reptiles, insectes et flore de la forêt départementale de Rolleboise 2009. 218 records from Schatzinsel Norderney. 50 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 9 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 154 records from Dermaptera in the icipe collection. 1188 records from Observations naturalistes de Philippe RAVAT. Inventaire entomologique du Morne Bigot. 17 records from Systematics of the New Zealand Weevil Etheophanus Broun (Curculionidae: Molytinae). 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 65 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 35 records from Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 2036 records from Données Odonates du Parc Naturel Régional du Perche. 2579 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (MZFC_OD). 4 records from A taxonomic synopsis of Chrysomydas Wilcox, Papavero & Pimentel (Diptera: Mydidae: Mydinae), with first bionomic records for the genus and description of a new species from Brazil. 8 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 3 records from The Genus Pseudopomyza (Diptera: Nerioidea) in Tasmania, with Description of a New Species. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 8 records from Synopsis of the Psychodidae (Diptera) fauna of Bulgaria. 25 records from Landschaftspflegehof (Berlin). 140 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 5 records from Bachpatenschaft Beeke. 4 records from One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae Meconematinae) from Guangxi, China. 461 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Parasitism of Hymenoepimecis manauara Pádua & Oliveira (Hymenoptera: Ichneumonidae: Pimplinae) on Leucauge henryi Mello-Leitão (Araneae: Tetragnathidae) in Brazilian Amazonian. 134 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 50 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 342 records from Données naturalistes de ROMET Nicolas. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 43 records from Artenvielfalt auf den Elbwiesen (Dessau). 6 records from Zanna robusticephalica sp. nov. (Hemiptera: Fulgoromorpha: Fulgoridae) from China, with comments on some ultrastructural characters of the new species. 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 66 records from The aquatic Coleoptera of Prince Edward Island, Canada: new records and faunal composition. 5 records from Discovery of a new species of Trieces (Hymenoptera: Ichneumonidae: Metopiinae) questioning the traditional delimitation between Trieces and Chorinaeus. 12 records from Revision of Khoikhoiinae (Hymenoptera, Braconidae). 291 records from Native Bee Baseline and Effects Monitoring on the Green Mountain National Forest 2015. 11 records from Lindau im Bodensee. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 44486 records from Estonian Nature Observations Database. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 127 records from New species, redescriptions and phylogenetic revision of tribe Dacini (Diptera: Tephritidae: Dacinae) from India based on morphological characters. 19 records from Review of the genus Trichactia Stein (Diptera: Tachinidae) in the Palaearctic Region, with the description of a new species from Iran and the East Mediterranean. 4782 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé à partir de 2016. 4 records from A new species of Selatosomus Stephens and the occurrence of Pristilophus melancholicus (Fabricius) in China (Coleoptera: Elateridae: Dendrometrinae). 41 records from Données de Rhône-Alpes transmises par Pascal Peyrache.. 38 records from Triebesbach (Zeulenroda-Triebes). 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 85 records from Larvas de Chironomidae (Insecta: Diptera) en un gradiente altitudinal de un río de la Sierra Nevada de Santa Marta - Colombia. 3 records from Zoology in the Middle East. 1 records from The mature larva and pupa of Tychius subsulcatus Tournier, 1847 (Coleoptera, Curculionidae), with comments on its biology and phylogenetic relationships. 5 records from The neotropical genus Sporrongia Gumovsky (Hymenoptera: Eulophidae) including two new species and the first biological record. 7207 records from Records from the RHS insect reference collection. 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 21937 records from Données de l'Observatoire de la Faune de Bourgogne. 2653 records from Taxonomy and distribution of pimpline parasitoids (Hymenoptera, Ichneumonidae, Pimplinae) in Ukraine. 20 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 30 records from Current condition of Bathypogon types (Diptera: Asilidae) described by Frank M Hull and housed in the South Australian Museum of Natural History with notes on other Bathypogon types. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 184 records from Données naturalistes 2019 de Bruno DAUGET. 356 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 13 records from Four new species of the genus Rhodesiella from Xizang Autonomous Region, China (Diptera: Chloropidae). 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 32117 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 58 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 106685 records from Tasmanian Museum and Art Gallery provider for OZCAM. 162 records from Colección de Entomología - Arthropoda. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 8 records from Immature stages of Neptis reducta Fruhstorfer, 1908 (Lepidoptera, Nymphalidae Neptini): morphology, ecology and food specialty. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 383 records from Insectos asociados a tres ventanas de la Orinoquia Colombiana - SULU I. 10 records from A large hornet mimic clearwing moth of the genus Lamellisphecia Kallies & Arita 2004 (Lepidoptera, Sesiidae) from Nanling, Guangdong, southern China. 1 records from A new species of Merothrips from the Dampa Tiger Reserve, Mizoram, India (Thysanoptera, Terebrantia). 10 records from Seeufer ehem. BUGA-Gelände. 55 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Cragbank and Wolfehopelee SSSI. 4724 records from Meetnetten.be - Egg counts for butterflies in Flanders, Belgium. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 471 records from Collection Lepidoptera SMF. 7 records from The genus Selasia Laporte, 1838 (Coleoptera: Elateridae: Agrypninae) in Sri Lanka. 3 records from An Update On The Stonefly Fauna (Insecta, Plecoptera) Of Maryland, Including New And Emended State Records And An Updated State Checklist. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 96512 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Description of a new Kempnyia Klapálek from Brazil (Plecoptera: Perlidae) with life stages associated using DNA barcodes. 11 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 64 records from Review of Poecilimon species with inflated pronotum: description of four new taxa within an acoustically diverse group. 222 records from Mexican species of the genus Orthocentrus (Hymenoptera, Ichneumonidae: Orthocentrinae). 50104 records from NDFF Butterfly Data. 11 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 82 records from Phenological Center - Insects (Karelia). 48 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 2 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 12 records from Brenz (Heidenheim). 13 records from Solomon Islands Ants 2015. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 39 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 63 records from Revision of Taurocerus (Heteroptera, Pentatomidae, Pentatomini). 2 records from A new genus of Pharaxonothinae from Australia (Coleoptera: Erotylidae). 260 records from Données naturalistes de William BATIFOIX. 76 records from Records of Invasive Non Native Species held on the Cofnod database. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 5 records from Two new species of Paratanytarsus Thienemann & Bause (Diptera: Chironomidae) from Oriental China. 4 records from Flightless Catapionus (Coleoptera: Curculionidae: Entiminae) in Southwest China survive the Holocene trapped on mountaintops: new species, unknown phylogeny and clogging taxonomy. 31 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 11 records from Schulgelände Lise Meitner Realschule (Paderborn). 12 records from Kurler Busch (Scharnhorst). 33 records from Systematic revision of Central American Calligrapha Chevrolat of the subgenus Erythrographa subgen. nov. (Coleoptera: Chrysomelidae, Chrysomelinae). 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 11 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 52 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 2 records from A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera Reduviidae) from Vietnam. 4 records from Données du/de la naturaliste Grosso Eric provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from White sea picoplankton Metagenome. 5425 records from The Keiichi Omoto Butterfly Collection, The University Museum, The University of Tokyo. Part I (Papilionidae: Baroniinae and Parnassiinae). 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 129891 records from Suivi Temporel des Rhopalocères de France (STERF). 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 6 records from Description of the Nymph of Tramea binotata (Rambur, 1842) (Odonata: Libellulidae). 4 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 6190 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 16 records from The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China. 6 records from Landwehrbach. 45 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 3 records from Birkenpilz. 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 27 records from Données naturalistes de Philippe VEILLON. 1406 records from Lauri Mällo private collection of Lepidoptera. 401 records from Données de VINCENT Alexis (SAPROX). 3 records from Review of the Swedish Enicospilus (Hymenoptera; Ichneumonidae; Ophioninae) with description of three new species and an illustrated key to species. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 107 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 655 records from Condon Fossil Collection - Oregon Museum of Natural and Cultural History. 1171 records from Glasgow Museums BRC: Chrysomelidae. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 27 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 43 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 15 records from City of Edinburgh Natural Heritage Service - Bonaly Moorland Moth Survey. 153 records from Taxonomy and host-plant relationships of the psyllid genus Mitrapsylla (Hemiptera: Psylloidea: Psyllidae) in Brazil. 82 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 24 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 31 records from Perlesta armitagei n. sp. (Plecoptera: Perlidae): More cryptic diversity in darkly pigmented Perlesta from the eastern Nearctic. 1 records from New Zealand Biodiversity Recording Network. 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 2 records from Nivå Bay species list, Zealand, Denmark. 2 records from Notes on Malagasy Discheramocephalus Johnson (Coleoptera: Ptiliidae). 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 108 records from A revision of the Patagonian predaceous midges of the subgenus Acanthohelea of Stilobezzia excluding the S. (A.) edwardsi group (Diptera: Ceratopogonidae). 8 records from Coleção de Porifera do Museu Nacional - UFRJ. 21 records from Distribution Of Neoperla (Plecoptera: Perlidae) In North Carolina, With New State Records For Three Species. 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 9 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 263 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 14 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 4 records from Two new cavernicolous Pselaphinae (Coleoptera: Staphylinidae) from southern China. 3 records from A peculiar new species of the genus Grammacephalus Haupt (Hemiptera Auchenorrhyncha: Cicadellidae: Deltocephalinae) from Madagascar. 9 records from A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea). 12012 records from Insect specimens of Toyota City Nature Sanctuary. 380 records from Nine new species of Enithares (Heteroptera: Notonectidae) from New Guinea, with distributional notes on other species and an updated world checklist. 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 570 records from Sudeniederung (Amt Neuhaus). 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 5 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 146 records from DREAL_PACA_-_N2000_-_Syndicat_Mixte_d'Aménagement_de_la_Vallée_de_la_Durance_2017_12_18. 3 records from Nouvelles fourmis de Madagascar.. 11822 records from Fife Nature Records Centre combined dataset. 39 records from A photographic catalog of Ceraphronoidea types at the Muséum national d’Histoire naturelle, Paris (MNHN), with comments on unpublished notes from Paul Dessart. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 3053 records from Heleomyzid Recording Scheme - data verified via iRecord. 9 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 17 records from A new species of Laurenceomyia Wagner & Stuckenberg, with a key to species and new records for Psychodidae (Diptera) from Uruguay. 14 records from Naturschutzgebiet Lochbusch-Königswiesen. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 70 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 25 records from Review of the genus Macropsis Lewis, 1836 (Homoptera: Auchenorrhyncha Cicadellidae: Eurymelinae: Macropsini) of Southeastern Kazakhstan with description of new species. 164 records from Données naturalistes de Philippe GOURDAIN (ANVL). 4 records from First record of tribe Laenini (Coleoptera, Tenebrionidae, Lagriinae) from Shanghai, with description of a new species of the genus Laena Dejean. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 4 records from Synopsis of Lasioglossum (Dialictus) Robertson, 1902 (Hymenoptera, Apoidea, Halictidae) in Japan, the Korean Peninsula and Taiwan. 11265 records from Distribución potencial en taxones hiperdiversos y poco conocidos (Insecta: Coleoptera: Scarabaeoidea): estimando la localización de nuevos taxones y el efecto de los cambios en los usos del suelo. 7814 records from Odonata de Veracruz. 1 records from BIRDRACE Niederlausitz-Team. 712 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 1 records from Review of the genus Suwallia (Plecoptera: Chloroperlidae) from China with description of Suwallia jihuae sp. nov. from Sichuan Province. 5635 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2015. 330 records from The water striders (Hemiptera: Heteroptera: Gerridae) of Costa Rica: new species, checklist, and new records. 42 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 77 records from Shannon Index and species richness for herbivores. 222 records from SNH Invertebrate Site Condition Monitoring 2013/14: River Spey - Insh Marshes SSSI. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 82 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 83 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 111 records from Andrena cyanura Cockerell, a valid North American species. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 696 records from Données du naturaliste Decroo Jean-Paul provenant de la base de donnée du SINP Île-de-France CETTIA. 56 records from CG04_2017_12_18. 1422 records from Reconocimiento de la biodiversidad de la Reserva de la Biósfera Calakmul: Odonata, psocóptera y díptera acuáticos (Insecta). 10 records from The Winter Stoneflies (Plecoptera: Capniidae) Of Mississippi. 88 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from Corynoneura Winnertz (Diptera, Chironomidae, Orthocladiinae) from Zhejiang Province, China. 47 records from Faberpark (Nürnberg/Stein). 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 126 records from Collection Ephemeroptera - SMF. 514 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 27 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 102437 records from Denver Museum of Nature & Science - Entomology. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 30 records from Onysius Broun: The First New Zealand Genus Of Promecheilidae (Coleoptera: Tenebrionoidea). 2737571 records from Insecta of Costa Rica (INBio). 6 records from Four new species of the leafhopper genus Riseveinus Li (Hemiptera: Cicadellidae: Evacanthinae) from China and Thailand. 55 records from Revision of the soft scale genus Paralecanium (Hemiptera: Coccomorpha: Coccidae) with the introduction of three new genera and twenty new species. 14 records from Tornoer Teich. 3 records from A pilot phylogeny study of Nemobiinae inferred from 18 S, 28 S and genes, with descriptions of two new genera and a new species from Hainan, China (Orthoptera: Grylloidea: Trigonidiidae). 15 records from Revision of the Chinese species of the genus Grouvellinus Champion, 1923 (Coleoptera: Elmidae). The G. acutus species group. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 7120 records from Collection of Hymenoptera. 39 records from Données du/de la naturaliste Sarouille Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 1 records from Two new species of the subgenus Brachyphytodecta Bechyně, 1948 (Coleoptera, Chrysomelidae, Gonioctena) from Sichuan, Southwest China. 19006 records from Weevil and Bark Beetle records via iRecord. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 113 records from Caracterización hidrogeológica para el diagnóstico ambiental de alternativas del proyecto hidroeléctrico San Bartolomé (ISAGEN y HMV).. 43 records from Three new species of the Encarsia inaron (Hymenoptera: Aphelinidae) species group from China with a key to Chinese species. 6 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 5 records from Nationalpark Harz Schul-AG Braunlage. 3 records from Undocumented beetle diversity in the Southeastern United States: a case study of the minute clubbed beetles (Coleoptera: Monotomidae). 13450 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 8 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 9 records from AKG-Gelände in Bensheim. 11 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 4 records from Three species of Hydrobaenus Fries (Diptera: Chironomidae: Orthocladiinae) from Belarus. 12 records from Tokunagaia Saether from China (Diptera: Chironomidae: Orthocladiinae). 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 629 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 1 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 9016 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 4 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 231 records from Review of Eotrogaspidia Lelej (Hymenoptera: Mutillidae: Trogaspidiini). 1 records from Limbodessus skalei sp. nov., a new diving beetle species from the west Papuan Archipelago (Coleoptera: Dytiscidae, Bidessini). 440 records from Wichita State University Collection. 67 records from Données naturalistes de Pierre-Alexis RAULT. 224 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 4 records from A new species and new records of Malagasy Megalopinus Eichelbaum (Coleoptera Staphylinidae, Megalopsidiinae), with notes on the sperm pump in rove beetles. 1 records from A new Symphoromyia in the Middle Eocene Baltic amber (Diptera: Rhagionidae). 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 638 records from pbzt_insect_biodiversity. 15 records from Taxonomic corrections for Asian Fingulus (Hemiptera: Heteroptera: Miridae). 23 records from Eudraces barclayi sp. nov., with some notes on the genus Eudraces Marshall (Coleoptera: Curculionidae: Entiminae: Myorhinini). 14 records from NZCS Upper Tapanahony Expedition 1991. 26 records from Streuobstwiese Stedar. 9 records from A new subspecies of Delias clathrata Rothschild, 1904 and records of other Delias species occurring on Mount Hagen, Papua New Guinea (Lepidoptera: Pieridae, Pierinae). 5 records from Calidolipeurus, new genus for Lipeurus megalops Piaget, 1880 (Phthiraptera: Ischnocera: Oxylipeurus-complex), with a redescription of the type species and a preliminary key to the Oxylipeurus-complex. 8 records from Two new species of Scymnini (Coleoptera: Coccinellidae) from Karnataka, India. 5 records from A new Central American genus of pleasing fungus beetles (Coleoptera: Erotylidae) from the Ischyrus-Megischyrus complex. 42 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 17 records from New Psocoptera (Hexapoda, Insecta) records from Belarus. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 35 records from Anthomyiidae, Fanniidae and Muscidae (Diptera) from the Juan Fernández Archipelago (Chile): 60 years after Willi Hennig’s contributions. 10 records from List of leaf beetles (Coleoptera: Chrysomelidae) from Lagodekhi reserve with new records for Transcaucasia and Georgia. 11 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 112 records from Comparative study of the meiobenthos in the Arctic region in 1991. 1 records from Fossil (GNHM-FO). 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 66 records from The national database for marine data (MADS). 7 records from A new species of the genus Morimotanthribus Senoh & Trýzna (Coleoptera Anthribidae) from South China. 10 records from A new genus and species of cricket from eastern Cuba: the first Antillean true Eneopterinae (Orthoptera: Gryllidae: Eneopterinae). 51 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 6 records from Coendutermes tucum Fontes (Isoptera, Termitidae, Nasutitermitinae): description of the imago caste and additional notes. 8 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 6 records from Kabelskebach (Kabelsketal, Saalkreis). 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1098 records from What bug is that. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 355 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 31 records from The genus Ochodaeus in Italy: taxonomy and distribution (Coleoptera: Scarabaeoidea: Ochodaeidae). 91 records from Dragonflies (Odonata) From The Sierras Of Tapirapeco And Unturan, In The Extreme South Of Venezuela. 103 records from Taxonomy and evolution of asymmetric male genitalia in the subgenus Ashima Chen (Diptera: Drosophilidae: Phortica Schiner), with descriptions of seven new species. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 145 records from Gelände des IVL (Zeckern). 9 records from Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species. 3 records from A new and likely extinct species of Antilissus Sharp, 1879 (Coleoptera: Zopheridae Colydiinae) from Makauwahi Cave, Kauai, Hawaiian Islands. 4 records from Warnowufer Groß Klein. 3 records from Paleotelmatoscopus, a proposed new genus for some fossil moth flies (Diptera Psychodidae, Psychodinae) in Eocene Baltic amber, with description of a new species. 7191 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 14 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 17 records from Six new species of the genus Bellulia Fibiger, 2008 from China and Cambodia (Lepidoptera, Erebidae, Hypenodinae). Taxonomic study of Micronoctuini Contribution III. 32144 records from Alterra (NL) - Entomofauna inventory in peat swamps. 32 records from Colección del Museo de Ciencias Naturales “José Lorca”. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 63 records from Contribution to the Ichneumoninae (Hymenoptera, Ichneumonidae) of Nepal. 2 records from Un nouveau genre et une nouvelle espèce de Cigale aphone du Malawi (Rhynchota, Cicadidae, Cicadettinae). 32 records from New data on the taxonomy, distribution and host plants of Australian Epermeniidae (Lepidoptera: Epermenioidea). 378 records from Données diverses du Parc naturel régional de Lorraine. 54 records from Jumping plant-lice (Hemiptera: Psylloidea) of Afghanistan. 25 records from Leafhopper subfamily Ledrinae of the Indian subcontinent: 1. Description of Yelahanka gen. nov. (Hemiptera: Cicadellidae) with seven new species and new combinations. 111 records from The bees (Hymenoptera: Apoidea) of the Maltese Islands. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 76 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 1 records from Extracellular DNA marine sediment Targeted Locus (Loci). 17 records from Further information on Lolibaia Gorbunov & Gurko, 2017 (Lepidoptera: Sesiidae: Synanthedonini) with description of three new species from tropical Africa. 1 records from Addendum to MANFRED R. ULITZKA (2019) Five new species of Rohrthrips (Thysanoptera: Rohrthripidae) from Burmese amber, and the evolution of Tubulifera wings. Zootaxa, 4585: 027 - 040.. 1 records from Notes on and key to the genus Phengaris (s. str.) (Lepidoptera, Lycaenidae) from mainland China with description of a new species. 3 records from A new species of Hemilea Loew and two new records of Trypetini (Diptera Tephritidae: Trypetinae) from India. 10 records from "Schwarzwassertal" bei Pobershau. 13117 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 396760 records from Museums Victoria provider for OZCAM. 49 records from Proper cleaning of keratin beetles reveals a cryptic species: Phoberus fumarius (Haaf, 1953) from southern Africa is reinstated as valid (Coleoptera: Trogidae). 3 records from Plan de vertebrados de la Patagonia. 633 records from Herbivorie_Pflanzenebene_2008. 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 18 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 67439 records from SysTax - Zoological Collections. 21 records from Trichromothrips genus-group (Thysanoptera, Thripidae) from China, with descriptions of three new species and ten new records. 5 records from Complementary Description Of Anacroneuria Izapa (Plecoptera: Perlidae) From Mexico. 6 records from Two new species of Ocyochterus (Heteroptera: Ochteridae) from Ecuador and Panama. 6070 records from Regroupement de données Rhopalocères. 34046 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 5 records from Données naturalistes de HENDOUX Frédéric. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 426 records from Danielsberg (Mölltal, Kärnten). 59 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 7897 records from LPO_PACA_2017_12_18. 348 records from Updated list of bumblebees (Hymenoptera: Apidae) from the Spanish Pyrenees with notes on their decline and conservation status. 4 records from Leptoceroidea (Insecta: Trichoptera: Integripalpia) from Serra do Caparaó, Southeast Brazil, including a new species of Atanatolica Mosely (Leptoceridae). 10 records from New species and findings of Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from Central Asia, with DNA barcoding of known species of the genus. 10 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 11 records from Pteroceraphron Dessart new to the USA (Hymenoptera: Ceraphronoidea). 132 records from Review of lady beetles in the Cycloneda germainii species complex (Coleoptera; Coccinellidae: Coccinellinae: Coccinellini) with descriptions of new and unusual species from Chile and surrounding countries. 630 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Liste des pays par taxon spécimen TOGO. 7 records from Discovery of leaf-mining Tischeriidae (Lepidoptera) in Colombia and their distribution in the Neotropics. 16 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 104 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) IX. The maculosa species-group, with descriptions of eighteen new species. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 4 records from Descriptions of three new species of Odonata from Brazil. 200 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 67 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2016. 74 records from Larval Taxonomy and Distribution of Genus Hydropsyche (Trichoptera: Hydropsychidae) in Northwestern Algeria. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 4769 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 5 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 6 records from Additions to the British list of Megaselia Rondani (Diptera: Phoridae), including two new species, from the crowns of ancient pollarded trees. 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 47 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 3 records from Two new species of the genus Odochilus Harold, 1877 (Coleoptera: Scarabaeidae Aphodiinae: Odochilini). 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 10 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 3 records from Kinderwald Hannover. 11 records from Three new species of Protosticta Selys, 1885 (Odonata: Zygoptera: Platystictidae) from the Western Ghats, India, with taxonomic notes on P. mortoni Fraser, 1922 and rediscovery of P. rufostigma Kimmins, 1958. 17 records from Abejas corbiculadas (Apidae) en el marco del proyecto Comparación morfológica de los Cuerpos Fungiformes en abejas. 1 records from Inventory of plant species through Benin (West Africa). 14502 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros (Heterocera). 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 175 records from Unser Schulgelände. 9640 records from Carabidae of Poland. 6 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 131 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 330280 records from University of Michigan Museum of Zoology, Division of Insects. 1 records from Non Fish Species Occurrence in ASEAN Region. 3 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 44604 records from Carnet B Centre - lot 2012. 3 records from Ohemoor (Hamburg/Norderstedt). 5 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 10798 records from Heteroptera collections of SW Finland. 21 records from Données de la structure Pie verte bio provenant de la base de donnée du SINP Île-de-France CETTIA. 242 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 2 records from First description of the last instar larva and pupa of the aquatic crane fly Limnorimarga limonioides (Alexander, 1945) (Diptera: Limoniidae). 204 records from Desarrollo de estudios ambientales dentro de las investigaciones para el futuro aprovechamiento hidroeléctrico del río Nare. 5 records from New Morphological Observations And Phylogenetic Placement Of Capnia Shasta (Plecoptera: Capniidae). 8 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 1 records from Review of the Oriental genus Neoperlops Banks, 1939 (Plecoptera: Perlidae). 3 records from Taxonomy and Natural History of Strumigenys thaxteri Wheeler and Strumigenys reticeps (Kempf) (Hymenoptera: Formicidae). 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 921 records from Distribution of aquatic beetles from the east of Morocco (Coleoptera, Polyphaga). 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 37 records from Données du/de la naturaliste FAUCHER Alexandre provenant de la base de donnée du SINP Île-de-France CETTIA. 72 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 12 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 7 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 7 records from A New Species Of Eupholus Boisduval (Coleoptera: Curculionidae: Entiminae) From West New Guinea. 746 records from Troides butterfly specimens at Museum Zoologi Bogor, Indonesia. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 32699 records from NMNH Paleobiology Specimen Records. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species and key to all known species of the genus Filchnerella Karny, 1908 from China (Orthoptera: Acridoidea, Pamphagidae). 1 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 3 records from Australian Formicidae.. 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 11 records from ENS inventaires - Parc naturel régional de Lorraine. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 44 records from Contributions to the knowledge of Umbrageocoris (Heteroptera: Lygaeoidea: Geocoridae). 21 records from New species of Narberdia Burke from México and Central America (Coleoptera: Curculionidae). 7 records from Örtzemündung (Stedden). 88 records from Revision of the New World Panthea Hübner (Lepidoptera, Noctuidae) with descriptions of 5 new species and 2 new subspecies. 21 records from Naturalis Biodiversity Center (NL) - Aves. 60221 records from National Stag Beetle Surveys (Great Stag Hunts). 4 records from Notes on the genus Psychonotis (Lepidoptera: Lycaenidae) from Western New Guinea (Papua and Papua Barat), with description of a new subspecies of P. melane (Joicey & Talbot, 1916). 22 records from Marine Offshore Seabed Survey data held by JNCC. 31 records from A review of Labidostomis species similar to L. longimana from southeastern Europe with descriptions of two new species from Greece and Turkey (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini). 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 10 records from Larvae of three East-Asian species of Nemoura (Plecoptera: Nemouridae). 1 records from A new genus and species of bark mantis from Thailand, with an updated key to the bark mantis genera of the Oriental region (Insecta: Mantodea). 1211 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 11704 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 6 records from Revision of the leafhopper genus Gurawa (Cicadellidae: Deltocephalinae: Chiasmini) from Pakistan with description of a new species. 47 records from Review of the Pacific leafhopper genus Hecaloidella (Hemiptera: Cicadellidae Deltocephalinae: Selenocephalini) with description of sixteen new species. 29977 records from UK Cranefly Recording Scheme - records verified via iRecord. 1004 records from Données odonates. 258 records from Malawi-Histeridae-Biodiversity-Data. 11 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 117 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2017. 228 records from Bishop's University Insect Collection (BUIC). 5 records from A new species of Dinotoperla Tillyard, 1921 from the Shoalhaven Catchment, New South Wales, Australia (Plecoptera: Gripopterygidae). 5 records from New species of Soa Enderlein, 1904 (Psocodea: ‘ Psocoptera’: Lepidopsocidae) from the Western Ghats of India. 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 8 records from Schulgarten Paul-Schneider-Schule, Münster. 1 records from Sediment metagenome. 9 records from New Oriental genera in the family Issidae (Hemiptera: Fulgoromorpha). 141143 records from BioFokus. 1156 records from Anymals+plants - Citizen Science Data. 2 records from DASSH Data Archive Centre volunteer sightings records. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 3 records from A new species of Velarifictorus Randell, 1964 (Orthoptera: Gryllidae: Gryllnae Modicoryllini) bearing similarities to the Landrevinae from China. 47 records from New species and additional data on the chewing louse genus Myrsidea (Phthiraptera: Menoponidae) from wild Neotropical Passeriformes (Aves). 61 records from Chronicle of Nature - Phenology of Insects of Central Forest State Nature Biosphere Reserve. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 19 records from Fossil (WSHN-FO). 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 33 records from Taxonomic revision of the Neotropical genus Caenopangonia Kröber, 1930 (Diptera: Tabanidae). 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 4 records from Yunnanosticta gen. nov., from Yunnan, a new genus from the Sinostictinae, with the description of two new species (Odonata: Zygoptera: Platystictidae). 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 17 records from Two new species of the genus Oryctopterus (Orthoptera: Stenopelmatidae: Oryctopinae) from India, with some notes on biology. 127 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 338 records from Annales du Musée d'Histoire Naturelle de Marseille (Zoologie). 1 records from Données espèces - Expertise IPE 28. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 36 records from What Is Capnia Umpqua Frison? (Plecoptera: Capniidae), Distribution And Variation Of Terminalia. 115 records from Review of six genera of Braconinae Nees (Hymenoptera, Braconidae) in China, with the description of eleven new species. 17 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 15428 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 2 records from A new species of the genus Polyphena Solovyev, 2014 (Lepidoptera: Limacodidae) from China. 6 records from Spider (NSMK-SP). 70912 records from CEDaR Online Recording. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 37 records from DSMZ Prokarya Collection Catalogue. 1 records from Westmead Mycology Culture Collection. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 282 records from National Biodiversity Data Bank. Observation records, 1900-2014. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 2418 records from NZCS Invertebrates Old Collection Before 1987. 33 records from Brentidae Acratini du massif du Mitaraka, en Guyane: une synthèse des données (Insecta, Coleoptera, Curculionoidea). 43 records from Generic relationships of New World Jerusalem crickets (Orthoptera: Stenopelmatoidea: Stenopelmatinae), including all known species of Stenopelmatus. 354 records from Données naturalistes de Delphine MONTAGNE. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 13 records from Contribution to the knowledge of the Prioninae (Coleoptera, Cerambycidae) from the Mizoram State (India), with the first report of the genus Megobaralipton Lepesme & Breuning and new records from the country. 2 records from VFD-H: Heidenrod: Pferdeweide Mürth. 12402 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 2 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 23 records from Taxonomic review of Coccobius species (Hymenoptera: Aphelinidae) from China, with notes on their use in biological control of scale insect pests (Hemiptera: Diaspididae), and description of a new species. 203 records from The InBIO Barcoding Initiative Database: Diptera 01. 5 records from First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther. 1236 records from Insect Collection (CeStuBio). 17 records from Nottekanal, Klasse 7 - 10. 77 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 8 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 301 records from Comunidad de hormigas en la Orinoquia Colombiana: estructura en tiempo y espacio. 1 records from The fossil crown wasp Electrostephanus petiolatus Brues in Baltic Amber (Hymenoptera, Stephanidae): designation of a neotype, revised classification, and a key to amber Stephanidae. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 5 records from The genus Enicospilus Stephens, 1835 (Hymenoptera, Ichneumonidae, Ophioninae) in Saudi Arabia, with twelve new species records and the description of five new species. 45 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 477 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 4 records from Données espèces - Expertise IPE 69. 8 records from Données taxonomiques et éthologiques nouvelles sur quatre espèces de Cigales du Sud thaïlandais (Rhynchota, Cicadoidea, Cicadidae). 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 9 records from Two new species of the genus Apsidophora Diakonoff, 1973 (Lepidoptera Tortricidae: Olethreutinae) from Thailand. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 12 records from Révision du genre Paradorodocia Machatschke, 1957 (Insecta, Coleoptera, Rutelidae, Adoretinae). 1 records from Flora und Fauna im Brexbachtal. 652 records from Insectos asociados a cultivos de Albahaca y Ají en Santa Marta. 6 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 111 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 11 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 1144 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5 records from Amphicoma gandhara, a new species of Glaphyridae (Coleoptera: Scarabaeoidea) from Swat District in northern Pakistan. 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 485667 records from Swiss National Grasshoppers Databank. 1 records from Inventaires complémentaires du Fort d'Aubervilliers (93). 2 records from Description of two new idiocerine leafhoppers of the genus Chinaocerus (Hemiptera: Cicadellidae) from southwestern China. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 13 records from New data and species of Thecomyia Perty, 1833 (Diptera: Sciomyzidae) from Mitaraka (French Guiana), with notes on the genus. 42 records from New species and records of Perlidae (Plecoptera) from Espírito Santo State, Brazil. 401 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 1 records from Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Chûjô & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae). 55 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 20375 records from Société_Française_d'Odonatologie_2017_12_18. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 11 records from Four new species of Brueelia Kéler, 1936 (Phthiraptera: Ischnocera) from African hosts, with a redescription of Nirmus bicurvatus Piaget, 1880. 59 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 28 records from WildesMoor bei Schwabstedt. 23 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 1 records from The InBIO Barcoding Initiative Database: Taxonomic notes on Portuguese Microlepidoptera II. Cochylimorpha punctiferana (Ragonot, 1881). 11516 records from Données du Parc Naturel Régional de la Haute Vallée de Chevreuse provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from FBIP: Offshore Benthic Macrofauna Data. 7 records from Revision of the genus Hormoserphus Townes, 1981 (Hymenoptera: Proctotrupidae), with description of Trachyserphus gen. n. and a new species. 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 5102 records from Données de ABGRALL Jean-François, Département Santé des Forêts, Ministère de l'agriculture. 7 records from Complementary Descriptions Of Kempnyia Gracilenta (Enderlein 1909) And Kempnyia Reticulata (Klapálek 1916) (Plecoptera: Perlidae). 3 records from First Record Of Pseudepipona Kazenasi Kurzenko, 1974 (Hymenoptera: Vespidae) From Mongolia. 8 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 41984 records from Repatriación de datos de los lepidópteros depositados en la Colección del McGuire Center for Lepidoptera and Biodiversity, Florida Museum of Natural History. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 1 records from Notes on the tribe Tongini, with description of a new species of the genus Orthophana from northern Vietnam (Hemiptera: Fulgoroidea: Nogodinidae). 6 records from New species of Platypalpus (Diptera: Hybotidae) from the Democratic Republic of the Congo. 8 records from Taxonomic review of Chin-wen Chen’s species described in the genus Smicromyrme (Hymenoptera: Mutillidae). 10 records from A new and an unrecorded species of the family Psychidae (Lepidoptera) from Korea, with an annotated catalogue. 33 records from Synopsis of warty leaf beetle genera of the world (Coleoptera, Chrysomelidae, Cryptocephalinae, Chlamisini). 1 records from First record of Caliscelis (Caliscelis) bonellii (L, 1807) (Hemiptera: Fulgoromorpha: Caliscelidae) from Turkey, with redescription of the species. 537 records from étude entomologique de la ZSC du Bois de Vaires. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 66 records from Weinberg Reichersdorf. 3904 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 4 records from Description of new species of Ambrosiodmus Hopkins and Dryocoetoides Hopkins (Curculionidae: Scolytinae: Xyleborini) from Mexico. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 1 records from A new species of Sweltsa (Plecoptera: Chloroperlidae) from Sichuan Province of southwestern China. 24 records from Nine new Agrilus (Coleoptera: Buprestidae, Agrilini) from Palaearctic and Oriental regions. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 11 records from Données de Lépidoptères de Bruno DAUGET - Dépt du LOIR-ET-CHER (41). 268 records from New records of Canadian Aleocharinae (Coleoptera, Staphylinidae). 1945 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 547 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 68 records from Revisão do gênero Paramecocephala Benvegnú, 1968 (Heteroptera, Pentatomidae). 13 records from Notes on types of Australian Chartocerus Motschulsky (Hymenoptera: Signiphoridae). 8 records from Four new species of the Oriental genus Elacatophora L. W. Schaufuss (Coleoptera Staphylinidae, Scydmaeninae). 1101660 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 39 records from Nothocasis rosariae sp. n., a new sylvicolous, montane species from southern Europe (Lepidoptera: Geometridae, Larentiinae). 1366 records from Données du programme 50000 observations pour la forêt. 10738 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 424 records from The Yponomeutidae of the Afrotropical region (Lepidoptera: Yponomeutoidea). 1 records from Données de mortalité de la faune par collision avec les véhicules sur le réseau routier de la DIR Centre-Est. 2 records from Studies in Guatemalan Ensifera: Mayacephalus (Orthoptera: Tettigoniidae) a new cone-headed katydid genus. 1 records from MfN - Fossil invertebrates IIa. 81 records from On the genus Berosus Leach (Coleoptera: Hydrophilidae) in the State of Roraima Brazil: description of three new species and new records. 89 records from Département_du_Var_2017_12_18. 2 records from A new species of the genus Onychopygia Beier (Orthoptera: Tettigoniidae: Pseudophyllinae) from Guatemala. 9 records from Cercopidae spittle-bugs (Hemiptera, Cicadomorpha) of Madagascar: a new species of Bourgoinrana and revision of the Locris species. 12 records from Projekt Wahner Heide. 36 records from Wildlife Observations Bardon Hill 31.5.09. 1 records from Omoleon jeanneli, new record from Kenya and a redescription (Neuroptera: Myrmeleontidae). 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 8 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 13513 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 17 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 12 records from Notes on a small collection of phaneropterine bush-crickets (Insecta: Orthoptera: Tettigonioidea) from Central and Southern Madagascar with the description of two new species. 4 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 139 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 2 records from A new genus and species of Neotropical gregarious braconine parasitoid (Hymenoptera: Braconidae) of a caterpillar (Lepidoptera: Hesperiidae). 1313 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 154 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 338 records from Occurrence data of Calliphorid flies held at the Natural History collection of the National Museums of Kenya. 16 records from Contribution to the knowledge of the genus Quedius S, 1829 of Siberia and Russian Far East (Coleoptera: Staphylinidae: Staphylinini: Quediina). 100 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 43 records from Sycacantha Diakonoff, 1959 from China, with the descriptions of three new species (Lepidoptera: Tortricidae: Olethreutinae). 112 records from WADFW PSAMP W1993. 4 records from HBRG Other Invertebrates Dataset. 6176911 records from iNaturalist Research-grade Observations. 17 records from First record of the genera Centistoides van Achterberg and Pygostolus Haliday (Hymenoptera: Braconidae) in Brazil, with the description of new species. 18 records from Two new species of the Amphinemura sinensis group (Plecoptera: Nemouridae) from southern China. 7 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 52 records from New taxa of the genus Phlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China, with comments on the importance to taxonomy of the left tegmen. 37 records from Bohemannia auriciliella (Nepticulidae) specimen data. 78 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 23 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 2 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 29 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 1 records from Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information. 14 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 2 records from A new species of Apostlethrips (Thysanoptera, Phlaeothripidae); an Australian genus from grass tussocks. 6 records from The Hydraenidae of Cuba (Insecta: Coleoptera) III. Description of two new hygropetric species of Hydraena Kugelann. 4 records from Horned and spiky: Tegotettix derijei sp. n. (Orthoptera: Tetrigidae) is a peculiar new pygmy grasshopper species from Mindanao. 46 records from A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China. 10 records from First record of the genus Setelacher Bouček (Hymenoptera: Eulophidae: Eulophinae) from the Afrotropical regionı with description of a new species. 80 records from An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea). 71 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 29 records from Description of the new genus Nebulene Volynkin & Černý, gen. nov., with a new species from Thailand and Vietnam (Lepidoptera, Erebidae, Arctiinae). 5155 records from Atlas of Life in the Coastal Wilderness. 2 records from Description of a new species of Miltochrista Hübner from Vietnam, with eight new combinations (Lepidoptera, Erebidae, Arctiinae). 217 records from Inventaire des odonates 2014. 33 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 6 records from New records of biting midges (Diptera: Ceratopogonidae) from the United Arab Emirates, with a description of a new species. 4 records from A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia. 9 records from Definition of the Bradysia luctifica group (Diptera, Sciaridae), with the description of five new species. 3 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 22 records from Données du naturaliste Julien Schwartz. 3 records from A new species of Misetus Wesmael, 1845 (Hymenoptera, Ichneumonidae, Ichneumoninae, Phaeogenini) from Italy, with updated key to the females of Palaearctic species. 4 records from Plant (NHMC-PL). 225 records from Orthoptera Tettigoniidae (Conocephalinae, Hexacentrinae, Phaneropterinae Mecopodinae, Hetrodinae) from some protected areas of Central African Republic. 1 records from Belarima violacea (Lucas, 1847) (Coleoptera, Chrysomelidae), a new genus and species for the European fauna. 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 2 records from Hildener Heide - Spörkelnbruch (Haan). 7 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 25 records from Descriptions, transference and new records of Lamiinae from Central and South America (Coleoptera, Cerambycidae). 10 records from A curious new genus of Keroplatini (Diptera: Keroplatidae) from Guatemala. 464 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 5 records from First record of Pulvinaria urbicola Cockerell (Hemiptera: Coccidae) from India, with a key to the Indian species of Pulvinaria Targioni Tozzetti. 1125 records from Données naturalistes de Damien AVRIL. 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 8 records from Contribution to the knowledge on the spider wasps genus Morochares Banks, 1934 (Hymenoptera: Pompilidae) from China. 3 records from The first species of Trichopsomyia Williston, 1888 (Diptera: Syrphidae) described from the Oriental region, with a discussion on the character states of the pilosity of the katepisternum. 38 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 4 records from Replacement names for two homonyms of Liothrips brevitubus Karny: one from California, the other for a species damaging Jatropha crops in Mexico. 72 records from 1915-2016 Department for Environment Food & Rural Affairs (Defra), Marine Strategy Framework Directive (MSFD) Collation of invasive non-indigenous species. 13 records from The first record of Cuculliaumbratica (Lepidoptera: Noctuidae) from Japan. 7 records from Further Descriptions Of Western North American Podmosta Larvae And Their Separation From Ostrocerca Larvae (Plecoptera: Nemouridae). 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 2 records from Naturalis Biodiversity Center (NL) - Echinodermata. 3 records from Lednia Tetonica, A New Species Of Stonefly From Wyoming (Plecoptera: Nemouridae). 112 records from Benthos counted on dredged samples during Valdivia cruise VA53. 751 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 96 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 13 records from Liether Park 2 (LMS), Klasse 6c. 1933 records from Carabidae of the European North-East of Russia. 10 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 403 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 3 records from Données naturalistes de Severine GUYOT. 14 records from Four new species of Mileewini leafhoppers (Hemiptera: Cicadellidae: Mileewinae) from China, with a checklist to Chinese species. 401 records from Noble Chafer: Post-BAP records from 1998 onwards. 276 records from Revision of the world Apenesia Westwood (Hymenoptera, Bethylidae). 7 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 15675 records from Specimen based records and geographic locations of carabid beetles (Coleoptera) collected mainly by Dr. Kazuo Tanaka. 1 records from Données naturalistes d'Anaïs MAS. 37 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 363 records from The cicadas (Hemiptera: Cicadidae) of India, Bangladesh, Bhutan, Myanmar, Nepal and Sri Lanka: an annotated provisional catalogue, regional checklist and bibliography. 11 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 6 records from Natura 2000 Complexe de l'étang de Lindre, forêt de Romersberg et zones voisines. 7 records from Redescriptions, new synonymy, new combination and new records of Bacis Dejean, 1836 and Oligocorynus Dejean, 1876 (Coleoptera: Erotylidae: Erotylinae) for Colombia. 5270 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 5 records from Contribution to the knowledge of the cavernicolous beetle genus Aspidaphaenops Uéno from Guizhou (Coleoptera: Carabidae: Trechinae). 67456 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 11 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part IV. Genera Eugnoriste Coquillett and Keilbachia Mohrig. 36 records from Review of Chinese species of the Oxylipeurus - complex (Phthiraptera: Philopteridae), with descriptions of two new genera and five new species. 6754 records from Dragonfly Ireland 2019 to 2024. 11 records from Machima itatiaia sp. nov.: a new species of lichen-mimic katydid (Orthoptera Tettigoniidae: Phaneropterinae) from the Brazilian Atlantic Forest. 61797 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 49 records from Küstenschutzwald. 1 records from BIRDRACE Griffin Wood Warblers. 34 records from Données espèces -expertise IQE 3. 179 records from Review of the rove beetle species of the subtribe Gyrophaenina Kraatz (Coleoptera, Staphylinidae) from New Brunswick, Canada: new species, provincial records and bionomic information. 41 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 9 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 4 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 141 records from New species and distribution records for Mexican and Central American Cerambycidae (Coleoptera). 17 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 711 records from The Muscidae (Diptera) of Armenia. 12 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 333 records from Données du naturaliste Arnaud Bak. 31 records from A Rare And Cryptic Endemic Of The Central Rocky Mountains, U. S. A: The Distribution Of The Arapahoe Snowfly, Arsapnia Arapahoe (Nelson & Kondratieff, 1988) (Plecoptera: Capniidae). 54 records from New records of the family Chalcididae (Hymenoptera: Chalcidoidea) from Egypt. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 56 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 61366 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 6 records from JCT AVH data. 9 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 50 records from Revision of the Agrilus humilis species-group (Coleoptera: Buprestidae: Agrilini) with description of thirteen new species from Southeastern Asia. 6 records from Aquatic Coleoptera of North Oman, with description of new species of Hydraenidae and Hydrophilidae. 2667 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 62 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 1 records from Paleobotany Specimens. 21 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 68768 records from CNIN/Lepidoptera. 67 records from Neospondylis upiformis from Anticosti Island (QC, Canada). 6541 records from Likona Invertebrates. 265 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 31 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 7 records from Données espèces - Expertise IPE 68. 1306 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 3 records from Review of the leafhopper genus Kalasha Distant (Hemiptera: Cicadellidae: Hylicinae). 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 7248 records from DBRC Hemiptera species records 1969 to 2015. 4 records from BB-Biodiversität a. 18733 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 78 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 4449 records from Fiocruz/CCER - Coleção de Ceratopogonidae. 844 records from Dorset SW Pilot species dataset. 47 records from Données du/de la naturaliste zeitouni kevin provenant de la base de donnée du SINP Île-de-France CETTIA. 208 records from Review of the African genera Arantia Stål and Goetia Karsch (Orthoptera: Tettigoniidae: Phaneropterinae). 34 records from First data on the bionomics of Leptochilus (Euleptochilus) limbiferus (Morawitz 1867) (Hymenoptera: Vespidae: Eumeninae), with taxonomic notes and new records. 1268 records from The Shigeru Eda Insect Collection of The University Museum, The University of Tokyo. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 2 records from Aquatic Coleoptera from Pakistan: faunistic and zoogeographical contribution (Coleoptera: Gyrinidae: Dytiscidae: Hydrophilidae). 7 records from New species and new behavioral data of Phlugiola Karny, 1907 (Orthoptera: Tettigoniidae: Meconematinae) from the Brazilian Amazonian Rainforest. 7032 records from FBIP: Systematics of South African Hymenoptera. 5 records from Contribution to the genus Chilocorus Leach, 1815 (Coleoptera: Coccinellidae: Chilocorini), with descriptions of two new species from China. 33 records from Konowia Brauns, 1884, and Monoxiphia, n. gen. (Hymenoptera, Xiphydriidae) Palaearctic woodwasps with simple tarsal claws on all legs. 30 records from Cumbria Non Native Invasive Species. 1 records from A new species of Ste
Keywords: GBIF; biodiversity; species occurrences